Host genetic background modulates early transcriptional responses to Neospora caninum infection in cattle - F. Fiorani; H. Carignano; A.M. Pardo; D.P. Moore; P.M. Corva (Research in Veterinary Science, 2026)

GollumFit: An icecube open-source framework for binned-likelihood neutrino telescope analyses - R. Abbasi; M. Ackermann; J. Adams; S.K. Agarwalla; J.A. Aguilar; M. Ahlers; J.M. Alameddine; N.M. Amin; K. Andeen; C. Argüelles; Y. Ashida; S. Athanasiadou; et al. (Computer Physics Communications, 2026)

From Genes to Greens: How Diet, Climate and Phylogeny Shape Freshwater Turtle Microbiotas - T. Franciscus Scheelings; Thi Thu Hao Van; Anthony Santoro; Louise M. Streeting; Christopher T. Ormond; James U. Van Dyke; Lee F. Skerratt; Robert J. Moore (Environmental Microbiology, 2026)
Reptile microbiotas remain poorly understood despite their importance for host ecology and evolution. This study investigated how diet, climate and evolutionary history shape the gut microbiota of 234 Australian freshwater turtles spanning 10 species, four climatic zones and contrasting trophic strategies. It was found that turtles' microbiotas were dominated by Pseudomonadota, Actinobacteriota and Bacteroidota. Microbial richness and evenness varied significantly among species, diets and climates. Carnivorous turtles exhibited greater bacterial diversity than omnivores, while individuals from oceanic and humid subtropical zones had higher diversity than those from semi‐arid and Mediterranean regions. Canonical Correspondence Analysis confirmed diet and climate as significant predictors of community composition, together explaining 2.76% of total variation. Omnivorous turtles were enriched in Bacteroidota, Myxococcota, Cyanobacteriota and Bacillota, whereas climatic effects drove distinct phylum‐level signatures across habitats. Host phylogeny showed a weak but significant signal of phylosymbiosis, indicating an evolutionary imprint on microbial structure. Collectively, these findings reveal that turtle microbiotas are shaped by a complex interplay between ecological and evolutionary forces, underscoring the importance of integrating microbial data into conservation strategies for Australia's increasingly threatened freshwater turtles.

Adaptation and Response in Drylands: A Dryland Research Agenda and Campaign Strategy - Andrew F. Feldman; Sasha C. Reed; Konrad Wessels; Dennis Ojima; David J. P. Moore; William K. Smith; Niall P. Hanan; Cibele Amaral; Flurin Babst; Joel A. Biederman; Marcy Litvak; Natasha MacBean; et al. (Global Change Biology, 2026)
Dryland ecosystems cover 41% of Earth's land surfaces, account for 44% of cultivated lands and 60% of food sources, and make large contributions to the global water and carbon cycles. However, these ecosystems are experiencing unprecedented extremes including heatwaves, floods, and droughts as well as hotter temperatures and often declining water resource availability. These ecosystems are some of the most challenging to monitor given their high temporal variability with rapid response to their environment as well as vast spatial variability with intermixing of different plant species and life forms amongst bare soil coverage. The Adaptation and Response in Drylands (ARID) campaign was selected by National Aeronautics and Space Administration (NASA) as a scoping study to develop a research agenda for a dryland field campaign. Here, we detail our ARID science research agenda and implementation plan that were developed based on an extensive community engagement effort in over 160 events with over a thousand scientists, land managers, and Tribal communities between 2023 and 2024. The selected science themes cover drought and climate variability, ecosystem structure, function, and biodiversity, carbon cycle interannual variability and trends, and social ecological systems (land management and adaptation). We then detail our remote sensing, modeling, and field‐based strategies to capture high temporal and high spatial resolution processes. Finally, our implementation strategy is presented which includes focus area selections in a core intensive western U.S. domain and distributed international domains. This strategy includes our overarching guiding principles of using multi‐temporal airborne acquisitions and super sites as well as enhancing land management in co‐development with end‐user partners. While originally developed for NASA, our ARID report creates a blueprint for any future dryland field campaign, at any scale, that can be implemented widely for foundational and applied science objectives.

Seasonal space use of gray wolves is concurrent with primary prey - Nathaniel H. Wehr; Seth A. Moore; Mark C. Romanski; Edmund J. Isaac; Kenneth F. Kellner; Todd M. Kautz; Joshua J. Millspaugh; Jerrold L. Belant (Oecologia, 2026)
Ecological seasonality describes the dynamic adaptation of species to changes in the biotic community and suggests predators should alter space use synchronously with seasonal prey availability. We assessed seasonal space use states (i.e., periods of similar movement and resource use) of mainland gray wolves ( Canis lupus ), moose ( Alces alces ), and white-tailed deer ( Odocoileus virginianus ) on the Grand Portage Indian Reservation, Minnesota, USA and island wolves and moose on Isle Royale National Park, Michigan, USA. We predicted mainland wolves would alter space use states (i.e., ecological seasons) corresponding to sympatric deer migration but island wolves would not, corresponding to their primary prey, non-migratory moose. We also predicted parturition would influence seasonal space use states in both systems. We used GPS collar locations recorded during 2008–2021, cluster analyses to temporally define space use states, and weighted resource selection functions to assess habitat selection during seasonal space use states. Mainland wolves exhibited two seasonal space use states with transitions between seasons coinciding with deer migration, and habitat selection varied among space use states for mainland wolves and their prey. Island wolves and moose did not alter their space use states seasonally, and their habitat selection differed from mainland populations. Parturition did not have a clear influence on seasonal space use. Our results suggest ecological seasonality is moderated by migration and linked to inter- and intra-guild species interactions via seasonal space use dynamics. These findings expand understanding of ecological seasonality at the community level and support the importance of multi-species management decisions.

The Level and Nature of Impairment on the Iowa Gambling Task Following Acquired Brain Injury: A Meta-analysis - Sammy Moore; Kristin Naragon-Gainey; Carmela F. Pestell; Rodrigo Becerra; Melissa T. Buelow; Danielle M. Fynn; Michael Weinborn (Neuropsychology Review, 2026)
The Iowa Gambling Task (IGT) is a popular measure of risky decision-making, but to date, no formal quantitative reviews have been conducted, focused exclusively on IGT performance amongst individuals with acquired brain injury (ABI). Therefore, this meta-analytic study firstly explored performance differences between individuals with ABI vs controls. Second, we extended this comparison by investigating differences in IGT scoring and interpretive approaches (e.g., total score vs later block analysis). Finally, we explored potential IGT performance moderators (e.g., average age). A total of 25 studies, containing 39 samples (total n = 2188), were included. Overall findings suggested that the IGT is sensitive to the presence of ABI, particularly non-TBI and medically confirmed TBI, which becomes evident by block 2 of 5. Medium effect sizes were obtained for IGT total score, as well as indicators using later blocks only. Performance moderators such as population type and region influenced IGT performance, whilst average age, average education, and proportion of males did not. These results indicate that the IGT is sensitive to decision-making impairment following ABI, although we conclude that further research is needed to confirm the IGT’s ability to detect impairment relative to specific brain regions.

Effects of sex and pre-exposure on Δ9-tetrahydrocannabinol (THC) vapor self-administration in rats - Catherine F. Moore; Elise M. Weerts (Psychopharmacology, 2026)

Proximal measurements of microwave reflectance using GNSS-IR track semi-arid grassland vegetation dynamics during greening and browning phases - Charles J. Devine; Russell L. Scott; Joel A. Biederman; Jinyang Du; David J.P. Moore; Andrew F. Feldman; Jessicca S. Guo; David K. Adams; William K. Smith (Agricultural and Forest Meteorology, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Current knowledge about neosporosis in Colombia - Piedad C. Rivas López; Samuel E. Idarraga-Bedoya; Luisa F. Mendoza-Morales; Jenny J. Chapparro-Gutiérrez; Agustín Góngora; Milton M. McAllister; Dadín P. Moore (Veterinary Research Communications, 2026)

Genetic Diversity Impacts Climate‐Induced Species Range Shifts - Brunno F. Oliveira; Romain Bertrand; Lise Comte; Jonathan Lenoir; Gaël Grenouillet; Lesley T. Lancaster; Jérôme Murienne; Sarah Diamond; Brett R. Scheffers; R. M. W. J. Bandara; Jake A. Lawlor; Nikki A. Moore; et al. (Ecology Letters, 2026)
Climate change threatens biodiversity when species cannot tolerate, adapt to, or track shifting environmental conditions to stay within their climatic niches. A major unresolved question is whether and how species' genetic diversity modulates these dynamics, buffering against range contractions or facilitating range expansions. To test this, we integrated the largest global databases of species range shifts and genetic diversity, encompassing 4673 range shift estimates for 1888 species with available genetic data, including insects, arachnids, birds, fish, and plants. We found that range shifting rates were significantly shaped by the interaction of genetic diversity and climate change velocity. Under rapid warming, species with higher genetic diversity exhibited reduced trailing edge contractions, likely reflecting enhanced evolutionary potential or reduced vulnerability to drift. Under moderate warming, species with higher genetic diversity shifted more rapidly at leading edges and range centroids, consistent with greater colonisation ability. Our study provides evidence that genetic diversity potentially enables persistence at the trailing edge and colonisation at the leading edge, with the magnitude of these effects varying depending on the velocity of climate change.

Informing spatial conservation prioritization with species’ traits - Liam A. Trethowan; Laura Jennings; Haerul Arifin; Renata Borosova; Gemma L. C. Bramley; Marie Briggs; Osanna Chu; Ruth P. Clark; Sally Dawson; Kiran L. Dhanjal‐Adams; Yance de Freitas; James Hartup; et al. (Conservation Biology, 2026)
New Guinea, the most botanically diverse island on the planet, is the location for one of the boldest conservation initiatives. The Manokwari Declaration aims to achieve 70% conservation designation for the Bird's Head Peninsula. This is 40% higher than the 2022 Global Biodiversity Framework target. However, there is a lack of species occurrence data to support evidence of where biodiversity can be best protected. To address this, we integrated plant trait data from taxonomic descriptions in species occurrence models that can inform conservation planning. Inclusion of traits improved the performance of co‐occurrence models of ∼800 plant species across the 100,000‐km 2 landscape. Traits generally improved model performance, but not all traits contributed equally (e.g., leaf size and red flower color most improved accuracy of occurrence prediction). Likewise, trait‐parameterized models tended to be most useful with rare species occurrence prediction, but this was inconsistent among traits. Under 70% protection, three‐quarters of the areas selected conserved trait diversity. Critically, trait diversity also increased the chances that areas at high risk of deforestation were selected as conservation priorities. Overall, we found that plant species’ traits, often key parameters of ecosystem function and resilience, improved spatial conservation planning.

Racial and ethnic disparities in environmental chemical exposures and hypertensive disorders of pregnancy: The ECHO-wide cohort study - Hongxiu Liu; Amii M. Kress; Emma X. Yu; Xuejuan Ning; Akhgar Ghassabian; Linda G. Kahn; Shilpi Mehta-Lee; Sara Brubaker; Akram Alshawabkeh; John Meeker; Carlos A. Camargo; Shakira F. Suglia; et al. (Environmental Pollution, 2026)

Identification of Dolly Varden (Salvelinus malma) in the Canadian Arctic east of the Mackenzie River - Spencer Y. Weinstein; Amanda Dumond; Tracey N. Loewen; James D. Reist; Matthew C. Hale; Colin P. Gallagher; Jean-Sébastien Moore; Les N. Harris; Ross F. Tallman; Robert Bajno; Zoya A. Martin; Paul M. Craig; et al. (Environmental Biology of Fishes, 2026)

The functional effects of African lions on co-occurring carnivores differ across species pairs and with changes in resource availability and lion abundance - Kristoffer T. Everatt; Leah Andresen; Jennifer F. Moore; James E. Hines; Graham I. H. Kerley (Oecologia, 2026)
Apex carnivores are known to regulate ecosystem structure and function, including via interactions with syntopic, competitively inferior carnivores. These effects may be dependent on relative carnivore density and resource availability or productivity. We investigated the functional effect of African lions as an apex carnivore on the presence of co-occurring large carnivore species across two adjoining National Parks that contrast in relative densities of carnivores and prey. We employed two-species occupancy models from track data to test statistical interactions between lions and the other syntopic large carnivore species, while accounting for each species’ habitat selection. We further investigated the influence of anthropogenic and natural variables on these co-occurrence dynamics. Our models revealed that the occurrence of each carnivore species was best predicted by access to their own key resources. We also found significant statistical interactions between lions and cheetahs, lions and leopards, and lions and spotted hyenas in resource-rich landscapes. Finally, we found limited support for the competition exclusion hypothesis between most species, with the exception of lion-African wild dog co-occurrence patterns. Species’ co-occurrence dynamics were all influenced by resource availability, with lion-leopard and lion-cheetah co-occurrence decreasing strongly with increasing resource availability. Most species co-occurrence declined with increasing occurrence of lions. The patterns revealed by this study improves predictions of how changes in resource availability and carnivore occurrence could impact carnivore community dynamics and the functional role of apex carnivores.

Micro‐Refuges or Ecological Traps: Context‐Dependent Effects of Rock Pools on Intertidal Biodiversity Across Latitudes - Louise B. Firth; Andrea Desiderato; Antony M. Knights; J. David Aguirre; Juan C. Astudillo; Juan C. Azofeifa‐Solano; David T. Bilton; Su Yin Chee; Hartvig C. Christie; Ronaldo A. Christofoletti; Amelia Curd; Katherine A. Dafforn; et al. (Global Ecology and Biogeography, 2026)
Aim We investigated how local‐scale environmental heterogeneity influences biodiversity patterns across broad biogeographic gradients, using intertidal microhabitats as a model system within one of the most environmentally stressful ecosystems on Earth. Location Intertidal habitats at 26 locations (two rocky shore sites per location) across six continents, spanning 98° of latitude (38°S to 60°N). Time Period 2019–2022. Major Taxa Studied Algae, sessile and mobile invertebrates. Methods We compared biodiversity and thermal environments across contrasting microhabitats (rock pools and adjacent emergent rock) along a latitudinal gradient, sampling during environmentally ‘milder’ and ‘harsher’ periods. Biodiversity was quantified using multiple richness metrics (mean, total, unique taxa) and functional diversity. Results Microhabitat differences strongly influenced biodiversity patterns across latitude. Rock pools consistently supported higher taxonomic and functional diversity than emergent rock, irrespective of sampling period, reflecting their ability to buffer thermal extremes, particularly under harsher conditions. Mean species richness exhibited a non‐linear, s‐shaped latitudinal pattern, with lowest values near the equator and higher richness at mid‐latitudes, diverging from classical Latitudinal Diversity Gradient expectations. Biodiversity differences between microhabitats were greatest in temperate regions and diminished at low latitudes, where extreme conditions constrained diversity across habitats. Main Conclusions Local environmental heterogeneity can substantially modify, and in some cases obscure large‐scale biodiversity patterns. By mediating exposure to environmental stress, intertidal microhabitats provide insight into how fine‐scale variability interacts with latitudinal stress gradients to shape biodiversity distributions. Incorporating microhabitat variability into biogeographic frameworks is important for understanding global biodiversity patterns and predicting ecological responses to climate change.

Accuracy of SeaHawk-HawkEye Ocean color CubeSat remote sensing reflectance products in globally distributed aquatic sites - Srinivas Kolluru; Sara Rivero-Calle; Philip J. Bresnahan; Susanne Kratzer; Timothy S. Moore; Thomas Schroeder; Sean Bailey; Alan Holmes; John M. Morrison; Gene F. Feldman; Liang Hong; Hiroto Higa; et al. (Remote Sensing of Environment, 2026)

Exploring Marine Mammal Cognition as a Conservation Tool - Gordon B. Bauer; Peter F. Cook; Heidi E. Harley; Jason Bruck; Mel Cosentino; Charles J. Deutsch; Nicola Erdsack; Wendi Fellner; Tabitha Gunnars; Heather Manitzas Hill; Sonia V. Kumar; Malin K. Lilley; et al. (Marine Mammal Science, 2026)
Cognition is an animal's real‐time adaptation system for responding to change. Rapid environmental change, often anthropogenic, is expanding the range and severity of challenges confronting wild animals. Effective conservation requires a multifaceted approach that includes animals' capacities. Large‐brained, long‐lived animals such as marine mammals often have extensive capability to adaptively modify their behavior due to their cognition, which comprises the mechanisms of information acquisition, processing, and flexible action. Consequently, current behavior need not be a final predictor of future behavior for these animals. This flexibility provides an underutilized and under examined point of leverage for humans interested in improving life outcomes for wild animals. In this team‐written, interdisciplinary paper, we argue that application of cognitive approaches may facilitate many conservation efforts directed toward marine mammals. Starting with a workshop on this topic at the 24th Biennial Conference on the Biology of Marine Mammals, scientists representing a wide range of disciplinary expertise addressed eight different conservation concerns for six marine mammal species and provided potential cognitive explanations of and interventions aimed at related behavior. Our treatment highlights the value of integrated laboratory and field research, and the importance of tight lines of communication between scientists and conservation managers.

The effects of cadmium and high fructose diet on metabolic and reproductive health in female CD-1 mice - Victoria R. Adams; Janice A. Dye; Micheal G. Narotsky; Makala L. Moore; Helen H. Nguyen; Aubrey L. Sasser; Kaberi P. Das; Lillian F. Strader; Joseph P. Pancras; Donna Hill; Chloe Davis; Wanda C. Williams; et al. (Food and Chemical Toxicology, 2025)

Species characteristics modulate tropical mammal responses to forest quality in Southeast Asia - Pradeep Raj Joshi; Asunción Semper-Pascual; Andrea F. Vallejo-Vargas; Douglas Sheil; Matthew S. Luskin; Jonathan Moore; Richard Bischof (Biological Conservation, 2025)

The Detroit volcanic province and the early evolution of the Hawaiian mantle plume - Reed B. Mershon; Aaron J. Pietruszka; Michael O. Garcia; Brian R. Jicha; Arron R. Steiner; Peng Jiang; J. Michael Rhodes; Michael J. Vollinger; Gregory F. Moore (Earth and Planetary Science Letters, 2025)

Connections between roots and soil health across agriculture management practices - E. Britt Moore; Mriganka De; Marcio R. Nunes; Debasish Saha; Virginia Jin; Lidong Li; Jane M. F. Johnson; Douglas L. Karlen; Marshall D. McDaniel (Plant and Soil, 2025)

Dual-strain detection of norovirus GI.1 and GII.4 in food samples using epitope-imprinted polymers - Amy Dann; Pankaj Singla; Jake McClements; Minji Kim; Sloane Stoufer; Robert D. Crapnell; Craig E. Banks; Shayan Seyedin; Mark Geoghegan; Christopher F. Blanford; Matthew D. Moore; Marloes Peeters (Analytica Chimica Acta, 2025)

New records of fishes from the Coral Sea Marine Park, Australia - Yi-Kai Tea; Tiffany L. Sih; Fenton Walsh; Timothy Bennett; Luiz A. Rocha; Ghislain Bardout; Amanda Hay; Kerryn Parkinson; Sally Reader; Indiana J. Riley; John J. Pogonoski; Jeffrey W. Johnson; et al. (Coral Reefs, 2025)
With an area covering just under 1 million km 2 , Australia’s Coral Sea Marine Park (CSMP) is among the largest marine protected areas globally. Yet, the demersal deep-reef fish fauna of the CSMP remains poorly described, due in part to its remote location, as well as its sheer size, much of which is inaccessible below conventional SCUBA diving depths. Recent remotely operated vehicle (ROV) explorations conducted by the Schmidt Ocean Institute provided an opportunity to explore the benthic ichthyofauna of deep mesophotic and rariphotic coral ecosystems. Contributions to the deep, demersal ichthyofauna of Australia’s CSMP are herein supplemented with an integrative dataset consisting of ROV imagery and specimen vouchers. Sixty-two new records of fishes from 26 families are reported from the CSMP. Of these, 45 are new Australian records, one of which is also a new family record for Australia. Four species are new records for the Southern Hemisphere, and 21 species are potentially new to science. We report new voucher material for 29 species, including several species previously identified as new for the CSMP with no voucher specimens.

Embracing social-ecological system complexity to promote climate-ready fisheries - Chris J. Harvey; Patricia M. Clay; Rebecca Selden; Stephanie K. Moore; Kelly S. Andrews; Yvonne L. deReynier; Anne H. Beaudreau; Owen R. Liu; Karma C. Norman; Jameal F. Samhouri; Lyall Bellquist; Merrick Burden; et al. (Reviews in Fish Biology and Fisheries, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Prenatal ozone exposure and child lung function: Exploring effect modification by oxidative balance score - Logan C. Dearborn; Marnie F. Hazlehurst; Melissa M. Melough; Adam A. Szpiro; Allison R. Sherris; Margaret A. Adgent; Yu Ni; Rosalind J. Wright; Neeta Thakur; Nicole R. Bush; Paul E. Moore; Christine T. Loftus; et al. (International Journal of Hygiene and Environmental Health, 2025)

Separating leaf area index from plant area index using semi-supervised classification of digital hemispheric canopy photographs: A case study of dryland vegetation - Jake Eckersley; Caitlin E. Moore; Sally E. Thompson; Michael Renton; Pauline F. Grierson (Agricultural and Forest Meteorology, 2025)

Prediction of daily childhood asthma exacerbation from ambient meteorological, environmental risk factors and respiratory viruses, Philadelphia, PA, 2011 to 2016 - Wanyu Huang; Lucy F. Robinson; Amy H. Auchincloss; Leah H. Schinasi; Kari Moore; Steven Melly; Christopher B. Forrest; Chén C. Kenyon; Anneclaire J. De Roos (Environmental Science and Pollution Research, 2025)
Childhood asthma exacerbation has multiple risk factors that occur concurrently in the environment — including extreme meteorological conditions, air pollution, aeroallergens, and respiratory virus infections. Few studies have predicted asthma exacerbation based on multiple time-varying environmental risk factors, together. In this study, we constructed an autoregressive integrated moving average (ARIMA) model to predict “high-risk” days for childhood asthma exacerbation in Philadelphia, PA from 2011 to 2016, during the aeroallergen season of each year, using a total of 28,540 asthma exacerbation case events identified from electronic health record (EHR) data. We selected predictors from quantile weighted sum regression (gQWS), incorporating temporal lags and season-stratification (early- vs. late-season), which were entered subsequently into multivariable ARIMA models. We found that daily nitrogen dioxide (NO 2 ), as well as monthly rhinovirus and respiratory syncytial virus (RSV) infection levels, were higher on the predicted “high-risk” days, as compared to days with lower childhood asthma exacerbation risk. The model performed better for late-season asthma exacerbation (July to October) than for early season (March to June). Future work and continued research is needed to facilitate local health guidelines pertaining to childhood asthma exacerbation.

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

Promoting best practices in ocean forecasting through an Operational Readiness Level - E. Alvarez Fanjul; S. Ciliberti; J. Pearlman; K. Wilmer-Becker; P. Bahurel; F. Ardhuin; A. Arnaud; K. Azizzadenesheli; R. Aznar; M. Bell; L. Bertino; S. Behera; et al. (Frontiers in Marine Science, 2024)
Predicting the ocean state in a reliable and interoperable way, while ensuring high-quality products, requires forecasting systems that synergistically combine science-based methodologies with advanced technologies for timely, user-oriented solutions. Achieving this objective necessitates the adoption of best practices when implementing ocean forecasting services, resulting in the proper design of system components and the capacity to evolve through different levels of complexity. The vision of OceanPrediction Decade Collaborative Center, endorsed by the UN Decade of Ocean Science for Sustainable Development 2021-2030, is to support this challenge by developing a “predicted ocean based on a shared and coordinated global effort” and by working within a collaborative framework that encompasses worldwide expertise in ocean science and technology. To measure the capacity of ocean forecasting systems, the OceanPrediction Decade Collaborative Center proposes a novel approach based on the definition of an Operational Readiness Level (ORL). This approach is designed to guide and promote the adoption of best practices by qualifying and quantifying the overall operational status. Considering three identified operational categories - production, validation, and data dissemination - the proposed ORL is computed through a cumulative scoring system. This method is determined by fulfilling specific criteria, starting from a given base level and progressively advancing to higher levels. The goal of ORL and the computed scores per operational category is to support ocean forecasters in using and producing ocean data, information, and knowledge. This is achieved through systems that attain progressively higher levels of readiness, accessibility, and interoperability by adopting best practices that will be linked to the future design of standards and tools. This paper discusses examples of the application of this methodology, concluding on the advantages of its adoption as a reference tool to encourage and endorse services in joining common frameworks.

Breed variability in the cellular mediated immune response to experimental Neospora caninum infection in heifers - F. Fiorani; B. Dallard; F.A. Cheuquepán; E. Sosa; A.M. Pardo; I. Gual; E.L. Morrell; M.S. Marín; S. Quintana; G.J. Cantón; B.S. Valentini; I.E. Echaide; et al. (Veterinary Immunology and Immunopathology, 2024)

A Comparison of Estimated Energy Intake Using Dietary Recalls vs. Predictive Equations Among African American Adults - C. Moore; F. Yan; J. Rooke (Journal of the Academy of Nutrition and Dietetics, 2024)

Corrigendum to ‘Evaluating the effect of expert elicitation techniques on population status assessment in the face of large uncertainty’ [J. Environ. Manag. 306 (2022) /114453] - Jennifer F. Moore; Julien Martin; Hardin Waddle; Evan H. Campbell Grant; Jill Fleming; Eve Bohnett; Thomas S.B. Akre; Donald J. Brown; Michael T. Jones; Jessica R. Meck; Kevin Oxenrider; Anthony Tur; et al. (Journal of Environmental Management, 2024)

Applying the Family Stress Model to responsive feeding and early obesity prevention - Cara F. Ruggiero; Kaitlin M. Trexberg; Amy M. Moore; Jennifer S. Savage (Appetite, 2024)

Episodic ozone exposure in Long-Evans rats has limited effects on cauda sperm motility and non-coding RNA populations - Brian N. Chorley; Gary R. Klinefelter; Gail M. Nelson; Lillian F. Strader; Helen H. Nguyen; Mette C. Schladweiler; Grant Palmer; Makala L. Moore; Rachel D. Grindstaff; William T. Padgett; Gleta K. Carswell; Anna A. Fisher; et al. (Reproductive Toxicology, 2024)

Applying the family stress model to responsive feeding and early obesity prevention - Cara F. Ruggiero; Kaitlin M. Trexberg; Amy M. Moore; Jennifer S. Savage (Appetite, 2024)

A warming western boundary current increases the prevalence of commercially disruptive parasites in broadbill swordfish - Jessica A. Bolin; Karen Evans; David S. Schoeman; Claire M. Spillman; Thomas S. Moore; Jason R. Hartog; Scott F. Cummins; Kylie L. Scales (Fisheries Oceanography, 2024)
Meat quality is of paramount importance in the fisheries and aquaculture industries, but the quality of seafood can be affected by environmental variability and change, creating uncertainties in the delivery of consistent, high‐end product. Reports from fishers operating in an Australian fishery catching broadbill swordfish ( Xiphias gladius ) suggest that anomalously warm waters are linked with myoliquefaction of muscle tissue. The condition affects the marketability of fish by turning the meat into a soft, mushy texture post‐mortem and is caused by infection by the myxozoan parasite Kudoa musculoliquefaciens . Here, we combine microscopy, molecular techniques and ecological modelling to explore potential environmental drivers of the prevalence and intensity of K. musculoliquefaciens in swordfish, as a first step in understanding how a warming ocean might exacerbate the risk of harvesting an infected swordfish and the resultant potential risk of myoliquefaction. We develop predictive dynamic risk surfaces on seasonal timescales, with results revealing both the likelihood of harvesting an infected swordfish and the intensity of parasite load increase during the Austral summer. The prevalence of the parasite further increases in the region dominated by the East Australian Current, when locally warm areas are atypically cool and when average monthly temperatures are more variable. These findings provide information useful in predicting the conditions under which the risk of harvesting infected swordfish might be intensified, enabling adaptation to climate change impacts and optimisation of decision‐making when fishing under risky conditions.

The COSPAR planetary protection policy for missions to Icy Worlds: A review of history, current scientific knowledge, and future directions - P.T. Doran; A. Hayes; O. Grasset; A. Coustenis; O. Prieto-Ballesteros; N. Hedman; O. Al Shehhi; E. Ammannito; M. Fujimoto; F. Groen; J.E. Moores; C. Mustin; et al. (Life Sciences in Space Research, 2024)

Associations of prenatal ambient air pollution exposures with asthma in middle childhood - Marnie F. Hazlehurst; Kecia N. Carroll; Paul E. Moore; Adam A. Szpiro; Margaret A. Adgent; Logan C. Dearborn; Allison R. Sherris; Christine T. Loftus; Yu Ni; Qi Zhao; Emily S. Barrett; Ruby H.N. Nguyen; et al. (International Journal of Hygiene and Environmental Health, 2024)

The JPL-GIM algorithm and products: multi-GNSS high-rate global mapping of total electron content - Léo Martire; Thomas F. Runge; Xing Meng; Siddharth Krishnamoorthy; Panagiotis Vergados; Anthony J. Mannucci; Olga P. Verkhoglyadova; Attila Komjáthy; Angelyn W. Moore; Robert F. Meyer; Byron A. Ijima; Donald W. Green (Journal of Geodesy, 2024)

Exploring the adoption of food safety measures in smallholder dairy systems in Ethiopia: implications for food safety and public health - Ndungu S. Nyokabi; Lilian Korir; Johanna F. Lindahl; Lisette Phelan; Gizachew Gemechu; Stefan Berg; Adane Mihret; James L. N. Wood; Henrietta L. Moore (Food Security, 2024)
Milk is highly perishable and can be a conduit for the transmission of zoonotic foodborne pathogens. This cross-sectional survey involving 159 farming households and 18 participant observations in participating farms was undertaken in Addis Ababa and surrounding areas in Oromia, Ethiopia to assess the adoption of food safety measures in smallholder farms. Adoption of food safety measures at the farm level influences milk quality and safety across the entire milk value chain, from “grass to glass”. This study considered the adoption of 36 different food safety measures (FSM) including animal health, milking hygiene, hygienic milk storage, and hygienic milking premises. A weighted food safety index (FSI, ranging from 0 to 100) was calculated for each household based on FSM adopted. Ordinary Least Squares linear regression was used to quantify the factors of FSM adoption by smallholder farmers. The overall food safety index ranged between 59.97—60.75. A majority of farmers may be classified as moderate adopters of FSM (index ranging between 30–70%). Farm and farmers’ characteristics such as herd size, farmer’s education level, farmer’s expertise in dairying, and participation of the farm in the formal milk value- chain, were shown to positively influence the level of adoption of FSM. Low farm-level adoption of FSM has food safety and public health implications as it can lead to milk contamination and, therefore, expose consumers to foodborne diseases. There is an imperative for policymakers to design and implement policies and intervention strategies that lead to increased farmer training related to livestock production and awareness of the important role that FSM adoption can play in improving food safety and public health.

Bringing traits back into the equation: A roadmap to understand species redistribution - Lise Comte; Romain Bertrand; Sarah Diamond; Lesley T. Lancaster; Malin L. Pinsky; Brett R. Scheffers; J. Alex Baecher; R. M. W. J. Bandara; I‐Ching Chen; Jake A. Lawlor; Nikki A. Moore; Brunno F. Oliveira; et al. (Global Change Biology, 2024)
Ecological and evolutionary theories have proposed that species traits should be important in mediating species responses to contemporary climate change; yet, empirical evidence has so far provided mixed evidence for the role of behavioral, life history, or ecological characteristics in facilitating or hindering species range shifts. As such, the utility of trait‐based approaches to predict species redistribution under climate change has been called into question. We develop the perspective, supported by evidence, that trait variation, if used carefully can have high potential utility, but that past analyses have in many cases failed to identify an explanatory value for traits by not fully embracing the complexity of species range shifts. First, we discuss the relevant theory linking species traits to range shift processes at the leading (expansion) and trailing (contraction) edges of species distributions and highlight the need to clarify the mechanistic basis of trait‐based approaches. Second, we provide a brief overview of range shift–trait studies and identify new opportunities for trait integration that consider range‐specific processes and intraspecific variability. Third, we explore the circumstances under which environmental and biotic context dependencies are likely to affect our ability to identify the contribution of species traits to range shift processes. Finally, we propose that revealing the role of traits in shaping species redistribution may likely require accounting for methodological variation arising from the range shift estimation process as well as addressing existing functional, geographical, and phylogenetic biases. We provide a series of considerations for more effectively integrating traits as well as extrinsic and methodological factors into species redistribution research. Together, these analytical approaches promise stronger mechanistic and predictive understanding that can help society mitigate and adapt to the effects of climate change on biodiversity.

David versus Goliath: Early career researchers in an unethical publishing system - Aurore Receveur; Jonathan Bonfanti; Stephanie D'Agata; Andrew J. Helmstetter; Nikki A. Moore; Brunno F. Oliveira; Cathleen Petit‐Cailleux; Erica Rievrs Borges; Marieke Schultz; Aaron N. Sexton; Devi Veytia (Ecology Letters, 2024)
The publish‐or‐perish culture in academia has catalysed the development of an unethical publishing system. This system is characterised by the proliferation of journals and publishers—unaffiliated with learned societies or universities—that maintain extremely large revenues and profit margins diverting funds away from the academic community. Early career researchers (ECRs) are particularly vulnerable to the consequences of this publishing system because of intersecting factors, including pressure to pursue high impact publications, rising publication costs and job insecurity. Moving towards a more ethical system requires that scientists advocate for structural change by making career choices that come with risks, many of which disproportionately impact ECRs. We illuminate major issues facing ECRs in Ecology and Evolution under the current publishing system, and propose a portfolio of actions to promote systemic change that can be implemented by ECRs and established researchers.

Expression and functional characterization of bovine receptor activator of NF-κB ligand (RANKL) - Ambre F. Chapuis; Omar A. Alfituri; Jayne C. Hope; Jo Stevens; Jo Moore; Kevin Mclean; Dorota Androscuk; Inga Dry (Veterinary Immunology and Immunopathology, 2024)

Megafire: An ambiguous and emotive term best avoided by science - Cathelijne R. Stoof; Jasper R. de Vries; Marc Castellnou Ribau; Mariña F. Fernández; David Flores; Julissa Galarza Villamar; Nicholas Kettridge; Desmond Lartey; Peter F. Moore; Fiona Newman Thacker; Susan J. Prichard; Pepijn Tersmette; et al. (Global Ecology and Biogeography, 2024)
Background As fire regimes are changing and wildfire disasters are becoming more frequent, the term megafire is increasingly used to describe impactful wildfires, under multiple meanings, both in academia and popular media. This has resulted in a highly ambiguous concept. Approach We analysed the use of the term ‘megafire’ in popular media to determine its origin, its developments over time, and its meaning in the public sphere. We subsequently discuss how relative the term ‘mega’ is, and put this in the context of an analysis of Portuguese and global data on fire size distribution. Results We found that ‘megafire’ originated in the popular news media over 20 years before it appeared in science. Megafire is used in a diversity of languages, considers landscape fires as well as urban fires, and has a variety of meanings in addition to size. What constitutes ‘mega’ is relative and highly context‐dependent in space and time, given variation in landscape, climate, and anthropogenic controls, and as revealed in examples from the Netherlands, Portugal and the Global Fire Atlas. Moreover, fire size does not equate to fire impact. Conclusion Given the diverse meanings of megafire in the popular media, we argue that redefining megafire in science potentially leads to greater disparity between science and practice. Megafire is widely used as an emotive term that is best left for popular media. For those wanting to use it in science, what constitutes a megafire should be defined by the context in which it is used, not by a metric of one‐size‐fits‐all.

Long-term ozone exposure and lung function in middle childhood - Marnie F. Hazlehurst; Logan C. Dearborn; Allison R. Sherris; Christine T. Loftus; Margaret A. Adgent; Adam A. Szpiro; Yu Ni; Drew B. Day; Joel D. Kaufman; Neeta Thakur; Rosalind J. Wright; Sheela Sathyanarayana; et al. (Environmental Research, 2024)

The Pacific water flow branches in the eastern Chukchi Sea - Robert S. Pickart; Peigen Lin; Frank Bahr; Leah T. McRaven; Jie Huang; Astrid Pacini; Kevin R. Arrigo; Carin J. Ashjian; Catherine Berchok; Mark F. Baumgartner; Kyoung-Ho Cho; Lee W. Cooper; et al. (Progress in Oceanography, 2023)

Bisphenols and phthalates in Australian wastewater: A statistical approach for estimating contributions from diffuse and point sources - Belinda Moore; Chang He; Emma Knight; Jochen F. Mueller; Benjamin Tscharke (Water Research, 2023)

Human milk: From complex tailored nutrition to bioactive impact on child cognition and behavior - Carolina de Weerth; Anna-Katariina Aatsinki; Meghan B. Azad; Frank F. Bartol; Lars Bode; Maria Carmen Collado; Amanda M. Dettmer; Catherine J. Field; Meagan Guilfoyle; Katie Hinde; Aniko Korosi; Hellen Lustermans; et al. (Critical Reviews in Food Science and Nutrition, 2023)

Direct sibling influence on feeding interactions in early childhood: Siblings as role models and caregivers - Cara F. Ruggiero; Amy M. Moore; Jennifer S. Savage (Appetite, 2023)

Characterization of lesions of nutritional congenital goitre in cattle - Luis A. Colque-Caro; Francisco Acuña; Laura S. Aguirre; Agustín Avellaneda-Cáceres; Claudio G. Barbeito; Marcelo Signorini; Dadin P. Moore; Juan F. Micheloud (Journal of Comparative Pathology, 2023)

Evaluation of evidence for interaction between PM2.5 and aeroallergens on childhood asthma exacerbation in Philadelphia, PA, 2011 to 2016 - Wanyu Huang; Leah H. Schinasi; Chén C. Kenyon; Amy H. Auchincloss; Kari Moore; Steven Melly; Lucy F. Robinson; Christopher B. Forrest; Anneclaire J. De Roos (Environmental Research, 2023)

Mercury in Neotropical birds: a synthesis and prospectus on 13 years of exposure data - Christopher J. Sayers; David C. Evers; Viviana Ruiz-Gutierrez; Evan Adams; Claudia M. Vega; Jessica N. Pisconte; Vania Tejeda; Kevin Regan; Oksana P. Lane; Abidas A. Ash; Reynold Cal; Stevan Reneau; et al. (Ecotoxicology, 2023)
Environmental mercury (Hg) contamination of the global tropics outpaces our understanding of its consequences for biodiversity. Knowledge gaps of pollution exposure could obscure conservation threats in the Neotropics: a region that supports over half of the world’s species, but faces ongoing land-use change and Hg emission via artisanal and small-scale gold mining (ASGM). Due to their global distribution and sensitivity to pollution, birds provide a valuable opportunity as bioindicators to assess how accelerating Hg emissions impact an ecosystem’s ability to support biodiversity, and ultimately, global health. We present the largest database on Neotropical bird Hg concentrations ( n = 2316) and establish exposure baselines for 322 bird species spanning nine countries across Central America, South America, and the West Indies. Patterns of avian Hg exposure in the Neotropics broadly align with those in temperate regions: consistent bioaccumulation across functional groups and high spatiotemporal variation. Bird species occupying higher trophic positions and aquatic habitats exhibited elevated Hg concentrations that have been previously associated with reductions in reproductive success. Notably, bird Hg concentrations were over four times higher at sites impacted by ASGM activities and differed by season for certain trophic niches. We developed this synthesis via a collaborative research network, the Tropical Research for Avian Conservation and Ecotoxicology (TRACE) Initiative, which exemplifies inclusive, equitable, and international data-sharing. While our findings signal an urgent need to assess sampling biases, mechanisms, and consequences of Hg exposure to tropical avian communities, the TRACE Initiative provides a meaningful framework to achieve such goals. Ultimately, our collective efforts support and inform local, scientific, and government entities, including Parties of the United Nations Minamata Convention on Mercury, as we continue working together to understand how Hg pollution impacts biodiversity conservation, ecosystem function, and public health in the tropics.

Electrohydraulic Shockwave for Treatment of Forelimb Superficial Digital Flexor Tendinitis and Proximal Suspensory Desmitis in Horses - Ahmed Khairoun; Jan F. Hawkins; George E. Moore; Timothy B. Lescun; Stephen B. Adams (Journal of Equine Veterinary Science, 2023)

Rapid prototyping for quantifying belief weights of competing hypotheses about emergent diseases - Ellen P. Robertson; Daniel P. Walsh; Julien Martin; Thierry M. Work; Christina A. Kellogg; James S. Evans; Victoria Barker; Aine Hawthorn; Greta Aeby; Valerie J. Paul; Brian K. Walker; Yasunari Kiryu; et al. (Journal of Environmental Management, 2023)

Effect of Taste Additives on the Palatability of Activated Charcoal: a Systematic Review - Elisabeth Canitrot; Alexis F. Turgeon; Lynne Moore; Ella Diendéré; Maude St-Onge (Journal of Medical Toxicology, 2023)

Drivers of the microbial metabolic quotient across global grasslands - A. C. Risch; S. Zimmermann; M. Schütz; E. T. Borer; A. A. D. Broadbent; M. C. Caldeira; K. F. Davies; N. Eisenhauer; A. Eskelinen; P. A. Fay; F. Hagedorn; J. M. H. Knops; et al. (Global Ecology and Biogeography, 2023)
Aim The microbial metabolic quotient (MMQ; mg CO 2 ‐C/mg MBC/h), defined as the amount of microbial CO 2 respired (MR; mg CO 2 ‐C/kg soil/h) per unit of microbial biomass C (MBC; mg C/kg soil), is a key parameter for understanding the microbial regulation of the carbon (C) cycle, including soil C sequestration. Here, we experimentally tested hypotheses about the individual and interactive effects of multiple nutrient addition (nitrogen + phosphorus + potassium + micronutrients) and herbivore exclusion on MR, MBC and MMQ across 23 sites (five continents). Our sites encompassed a wide range of edaphoclimatic conditions; thus, we assessed which edaphoclimatic variables affected MMQ the most and how they interacted with our treatments. Location Australia, Asia, Europe, North/South America. Time period 2015–2016. Major taxa Soil microbes. Methods Soils were collected from plots with established experimental treatments. MR was assessed in a 5‐week laboratory incubation without glucose addition, MBC via substrate‐induced respiration. MMQ was calculated as MR/MBC and corrected for soil temperatures (MMQsoil). Using linear mixed effects models (LMMs) and structural equation models (SEMs), we analysed how edaphoclimatic characteristics and treatments interactively affected MMQsoil. Results MMQsoil was higher in locations with higher mean annual temperature, lower water holding capacity and lower soil organic C concentration, but did not respond to our treatments across sites as neither MR nor MBC changed. We attributed this relative homeostasis to our treatments to the modulating influence of edaphoclimatic variables. For example, herbivore exclusion, regardless of fertilization, led to greater MMQsoil only at sites with lower soil organic C ( Main conclusions Our results pinpoint the main variables related to MMQsoil across grasslands and emphasize the importance of the local edaphoclimatic conditions in controlling the response of the C cycle to anthropogenic stressors. By testing hypotheses about MMQsoil across global edaphoclimatic gradients, this work also helps to align the conflicting results of prior studies.

Actinium and radium fluxes from the seabed in the northeast Pacific Basin - Nathaniel Kemnitz; Douglas E. Hammond; Paul Henderson; Emilie Le Roy; Matthew Charette; Willard Moore; Robert F. Anderson; Martin Q. Fleisher; Anne Leal; Erin Black; Christopher T. Hayes; Jess Adkins; et al. (Marine Chemistry, 2023)

Compactive deformation of incoming calcareous pelagic sediments, northern Hikurangi subduction margin, New Zealand: Implications for subduction processes - Maomao Wang; Philip M. Barnes; Julia K. Morgan; Rebecca E. Bell; Gregory F. Moore; Ming Wang; Ake Fagereng; Heather Savage; Davide Gamboa; Robert N. Harris; Stuart Henrys; Joshu Mountjoy; et al. (Earth and Planetary Science Letters, 2023)

Long‐distance migration is a major factor driving local adaptation at continental scale in Coho salmon - Quentin Rougemont; Amanda Xuereb; Xavier Dallaire; Jean‐Sébastien Moore; Eric Normandeau; Alysse Perreault‐Payette; Bérénice Bougas; Eric B. Rondeau; Ruth E. Withler; Donald M. Van Doornik; Penelope A. Crane; Kerry A. Naish; et al. (Molecular Ecology, 2023)
Inferring the genomic basis of local adaptation is a long‐standing goal of evolutionary biology. Beyond its fundamental evolutionary implications, such knowledge can guide conservation decisions for populations of conservation and management concern. Here, we investigated the genomic basis of local adaptation in the Coho salmon ( Oncorhynchus kisutch ) across its entire North American range. We hypothesized that extensive spatial variation in environmental conditions and the species’ homing behaviour may promote the establishment of local adaptation. We genotyped 7829 individuals representing 217 sampling locations at more than 100,000 high‐quality RADseq loci to investigate how recombination might affect the detection of loci putatively under selection and took advantage of the precise description of the demographic history of the species from our previous work to draw accurate population genomic inferences about local adaptation. The results indicated that genetic differentiation scans and genetic–environment association analyses were both significantly affected by variation in recombination rate as low recombination regions displayed an increased number of outliers. By taking these confounding factors into consideration, we revealed that migration distance was the primary selective factor driving local adaptation and partial parallel divergence among distant populations. Moreover, we identified several candidate single nucleotide polymorphisms associated with long‐distance migration and altitude including a gene known to be involved in adaptation to altitude in other species. The evolutionary implications of our findings are discussed along with conservation applications.

Resource dilution in maternal feeding practices after birth of a secondborn - Cara F. Ruggiero; Amy M. Moore; Michele E. Marini; Stephen R. Kodish; Damon E. Jones; Susan M. McHale; Jennifer S. Savage (Appetite, 2023)

Long-term N-addition alters the community structure of functionally important N-cycling soil microorganisms across global grasslands - Beat Frey; Barbara Moser; Bjorn Tytgat; Stephan Zimmermann; Juan Alberti; Lori A. Biederman; Elizabeth T. Borer; Arthur A.D. Broadbent; Maria C. Caldeira; Kendi F. Davies; Nico Eisenhauer; Anu Eskelinen; et al. (Soil Biology and Biochemistry, 2023)

Geochemical and paleoenvironmental characteristics of upper Neoproterozoic ore-hosting black shales in the Bafq metallogenic zone, Central Iran - E. Mahmoudi; S. Asadi; F. Moore (Australian Journal of Earth Sciences, 2022)

Microplastics in industrial and urban areas in South-West Iran - Z. Mokhtarzadeh; B. Keshavarzi; F. Moore; R. Busquets; M. Rezaei; E. Padoan; F. Ajmone-Marsan (International Journal of Environmental Science and Technology, 2022)

Global estimates of the extent and production of macroalgal forests - Carlos M. Duarte; Jean‐Pierre Gattuso; Kasper Hancke; Hege Gundersen; Karen Filbee‐Dexter; Morten F. Pedersen; Jack J. Middelburg; Michael T. Burrows; Kira A. Krumhansl; Thomas Wernberg; Pippa Moore; Albert Pessarrodona; et al. (Global Ecology and Biogeography, 2022)
Aim Macroalgal habitats are believed to be the most extensive and productive of all coastal vegetated ecosystems. In stark contrast to the growing attention on their contribution to carbon export and sequestration, understanding of their global extent and production is limited and these have remained poorly assessed for decades. Here we report a first data‐driven assessment of the global extent and production of macroalgal habitats based on modelled and observed distributions and net primary production (NPP) across habitat types. Location Global coastal ocean. Time period Contemporary. Major taxa studied Macroalgae. Methods Here we apply a comprehensive niche model to generate an improved global map of potential macroalgal distribution, constrained by incident light on the seafloor and substrate type. We compiled areal net primary production (NPP) rates across macroalgal habitats from the literature and combined this with our estimates of the global extent of these habitats to calculate global macroalgal NPP. Results We show that macroalgal forests are a major biome with a global area of 6.06–7.22 million km 2 , dominated by red algae, and NPP of 1.32 Pg C/year, dominated by brown algae. Main conclusions The global macroalgal biome is comparable, in area and NPP, to the Amazon forest, but is globally distributed as a thin strip around shorelines. Macroalgae are expanding in polar, subpolar and tropical areas, where their potential extent is also largest, likely increasing the overall contribution of algal forests to global carbon sequestration.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Bridge to the future: Important lessons from 20 years of ecosystem observations made by the OzFlux network - Jason Beringer; Caitlin E. Moore; Jamie Cleverly; David I. Campbell; Helen Cleugh; Martin G. De Kauwe; Miko U. F. Kirschbaum; Anne Griebel; Sam Grover; Alfredo Huete; Lindsay B. Hutley; Johannes Laubach; et al. (Global Change Biology, 2022)
In 2020, the Australian and New Zealand flux research and monitoring network, OzFlux, celebrated its 20 th anniversary by reflecting on the lessons learned through two decades of ecosystem studies on global change biology. OzFlux is a network not only for ecosystem researchers, but also for those ‘next users’ of the knowledge, information and data that such networks provide. Here, we focus on eight lessons across topics of climate change and variability, disturbance and resilience, drought and heat stress and synergies with remote sensing and modelling. In distilling the key lessons learned, we also identify where further research is needed to fill knowledge gaps and improve the utility and relevance of the outputs from OzFlux. Extreme climate variability across Australia and New Zealand (droughts and flooding rains) provides a natural laboratory for a global understanding of ecosystems in this time of accelerating climate change. As evidence of worsening global fire risk emerges, the natural ability of these ecosystems to recover from disturbances, such as fire and cyclones, provides lessons on adaptation and resilience to disturbance. Drought and heatwaves are common occurrences across large parts of the region and can tip an ecosystem's carbon budget from a net CO 2 sink to a net CO 2 source. Despite such responses to stress, ecosystems at OzFlux sites show their resilience to climate variability by rapidly pivoting back to a strong carbon sink upon the return of favourable conditions. Located in under‐represented areas, OzFlux data have the potential for reducing uncertainties in global remote sensing products, and these data provide several opportunities to develop new theories and improve our ecosystem models. The accumulated impacts of these lessons over the last 20 years highlights the value of long‐term flux observations for natural and managed systems. A future vision for OzFlux includes ongoing and newly developed synergies with ecophysiologists, ecologists, geologists, remote sensors and modellers.

Globally, tree fecundity exceeds productivity gradients - Valentin Journé; Robert Andrus; Marie‐Claire Aravena; Davide Ascoli; Roberta Berretti; Daniel Berveiller; Michal Bogdziewicz; Thomas Boivin; Raul Bonal; Thomas Caignard; Rafael Calama; Jesús Julio Camarero; et al. (Ecology Letters, 2022)
Lack of tree fecundity data across climatic gradients precludes the analysis of how seed supply contributes to global variation in forest regeneration and biotic interactions responsible for biodiversity. A global synthesis of raw seedproduction data shows a 250‐fold increase in seed abundance from cold‐dry to warm‐wet climates, driven primarily by a 100‐fold increase in seed production for a given tree size. The modest (threefold) increase in forest productivity across the same climate gradient cannot explain the magnitudes of these trends. The increase in seeds per tree can arise from adaptive evolution driven by intense species interactions or from the direct effects of a warm, moist climate on tree fecundity. Either way, the massive differences in seed supply ramify through food webs potentially explaining a disproportionate role for species interactions in the wet tropics.

Cannabinoid tetrad effects of oral Δ9-tetrahydrocannabinol (THC) and cannabidiol (CBD) in male and female rats: sex, dose-effects and time course evaluations - Catherine F. Moore; Elise M. Weerts (Psychopharmacology, 2022)

High-temperature oxidation of proximal basaltic pyroclasts, 1886 Tarawera, New Zealand - Hannah C. Moore; Rebecca J. Carey; Bruce F. Houghton; Martin Jutzeler; James D. L. White (Bulletin of Volcanology, 2022)
Microlite crystallization in erupting basalt can occur in the conduit, in flight, or in situ after deposition. Distinguishing the products of primary versus secondary (post-fragmentation) crystallization can be challenging in near-vent environments, but is vital for interpreting shallow conduit conditions from pyroclast textures. Here, we examine pyroclasts of the 1886 basaltic Plinian eruption of Tarawera volcano, New Zealand, to assess the roles of primary versus secondary crystallization of microlites. Lapilli and ash were selected from (a) an ultra-proximal section (T47), < 100 m from vent, which is dominated by pyroclasts derived from the Plinian jet and column margin, and (b) a medial fall deposit section (T43), 2.5 km from the fissure, which contains products from the umbrella cloud. Strong contrasts in pyroclast groundmass crystallinities exist between sections, from near-holocrystalline (90–97% void-free corrected; VFC) in T47 pyroclasts to highly crystalline (77–83% VFC) in T43 pyroclasts. Subhedral-euhedral Fe–Ti microlites (< 3 μm) are ubiquitous and abundant in T47 pyroclasts, whereas they are virtually absent in T43 pyroclasts. Olivine is present in both T47 and T43 pyroclasts but evidence of its subsolidus transformation is only seen in T47 clasts, whereas in T43 clasts olivine is fresh. Near-complete crystallization of the groundmass and subsolidus transformation of olivine in the ultraproximal T47 clasts are evidence that post-depositional modification of primary pyroclast textures occurred in ultra-proximal environments at Tarawera as a response to high residual temperatures and oxidizing conditions, aided by short transport times of relatively coarse ejecta at high accumulation rates, likely supplemented by intense vent-derived heat. Ultra-proximal basaltic eruption products can continue to crystallize after deposition and are thus unlikely to be faithful indictors of shallow conduit magmatic processes; we recommend the use of medial and distal products instead.

Nutrient identity modifies the destabilising effects of eutrophication in grasslands - Oliver Carroll; Evan Batzer; Siddharth Bharath; Elizabeth T. Borer; Sofía Campana; Ellen Esch; Yann Hautier; Timothy Ohlert; Eric W. Seabloom; Peter B. Adler; Jonathan D. Bakker; Lori Biederman; et al. (Ecology Letters, 2022)
Nutrient enrichment can simultaneously increase and destabilise plant biomass production, with co‐limitation by multiple nutrients potentially intensifying these effects. Here, we test how factorial additions of nitrogen (N), phosphorus (P) and potassium with essential nutrients (K+) affect the stability (mean/standard deviation) of aboveground biomass in 34 grasslands over 7 years. Destabilisation with fertilisation was prevalent but was driven by single nutrients, not synergistic nutrient interactions. On average, N‐based treatments increased mean biomass production by 21–51% but increased its standard deviation by 40–68% and so consistently reduced stability. Adding P increased interannual variability and reduced stability without altering mean biomass, while K+ had no general effects. Declines in stability were largest in the most nutrient‐limited grasslands, or where nutrients reduced species richness or intensified species synchrony. We show that nutrients can differentially impact the stability of biomass production, with N and P in particular disproportionately increasing its interannual variability.

Preface: to the special issue: photochemistry and electrochemistry of natural and artificial photosynthesis - Gary F. Moore; Elizabeth Young (Photosynthesis Research, 2022)

Photoelectrochemistry of metalloporphyrin-modified GaP semiconductors - Daiki Nishiori; Brian L. Wadsworth; Edgar A. Reyes Cruz; Nghi P. Nguyen; Lillian K. Hensleigh; Timothy Karcher; Gary F. Moore (Photosynthesis Research, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Addressing the welfare needs of farmed lumpfish: Knowledge gaps, challenges and solutions - Carlos Garcia de Leaniz; Carolina Gutierrez Rabadan; Sara I. Barrento; Rebecca Stringwell; Paul N. Howes; Ben A. Whittaker; Jessica F. Minett; Robert G. Smith; Craig L. Pooley; Ben J. Overland; Leigh Biddiscombe; Richard Lloyd; et al. (Reviews in Aquaculture, 2022)
Lumpfish ( Cyclopterus lumpus L.) are increasingly being used as cleaner fish to control parasitic sea lice, one of the most important threats to salmon farming. However, lumpfish cannot survive feeding solely on sea lice, and their mortality in salmon net‐pens can be high, which has welfare, ethical and economic implications. The industry is under increasing pressure to improve the welfare of lumpfish, but little guidance exists on how this can be achieved. We undertook a knowledge gap and prioritisation exercise using a Delphi approach with participants from the fish farming sector, animal welfare, academia and regulators to assess consensus on the main challenges and potential solutions for improving lumpfish welfare. Consensus among participants on the utility of 5 behavioural and 12 physical welfare indicators was high (87–89%), reliable (Cronbach's alpha = 0.79, 95CI = 0.69–0.92) and independent of participant background. Participants highlighted fin erosion and body damage as the most useful and practical operational welfare indicators, and blood parameters and behavioural indicators as the least practical. Species profiling revealed profound differences between Atlantic salmon and lumpfish in relation to behaviour, habitat preferences, nutritional needs and response to stress, suggesting that applying a common set of welfare standards to both species cohabiting in salmon net‐pens may not work well for lumpfish. Our study offers 16 practical solutions for improving the welfare of lumpfish and illustrates the merits of the Delphi approach for achieving consensus among stakeholders on welfare needs, targeting research where is most needed and generating workable solutions.

Fine root dynamics across pantropical rainforest ecosystems - Walter Huaraca Huasco; Terhi Riutta; Cécile A. J. Girardin; Fernando Hancco Pacha; Beisit L. Puma Vilca; Sam Moore; Sami W. Rifai; Jhon del Aguila‐Pasquel; Alejandro Araujo Murakami; Renata Freitag; Alexandra C. Morel; Sheleme Demissie; et al. (Global Change Biology, 2021)
Fine roots constitute a significant component of the net primary productivity (NPP) of forest ecosystems but are much less studied than aboveground NPP. Comparisons across sites and regions are also hampered by inconsistent methodologies, especially in tropical areas. Here, we present a novel dataset of fine root biomass, productivity, residence time, and allocation in tropical old‐growth rainforest sites worldwide, measured using consistent methods, and examine how these variables are related to consistently determined soil and climatic characteristics. Our pantropical dataset spans intensive monitoring plots in lowland (wet, semi‐deciduous, and deciduous) and montane tropical forests in South America, Africa, and Southeast Asia ( n = 47). Large spatial variation in fine root dynamics was observed across montane and lowland forest types. In lowland forests, we found a strong positive linear relationship between fine root productivity and sand content, this relationship was even stronger when we considered the fractional allocation of total NPP to fine roots, demonstrating that understanding allocation adds explanatory power to understanding fine root productivity and total NPP. Fine root residence time was a function of multiple factors: soil sand content, soil pH, and maximum water deficit, with longest residence times in acidic, sandy, and water‐stressed soils. In tropical montane forests, on the other hand, a different set of relationships prevailed, highlighting the very different nature of montane and lowland forest biomes. Root productivity was a strong positive linear function of mean annual temperature, root residence time was a strong positive function of soil nitrogen content in montane forests, and lastly decreasing soil P content increased allocation of productivity to fine roots. In contrast to the lowlands, environmental conditions were a better predictor for fine root productivity than for fractional allocation of total NPP to fine roots, suggesting that root productivity is a particularly strong driver of NPP allocation in tropical mountain regions.

CYP450 polymorphisms and clinical pharmacogenetics of ibuprofen after lower third molar extraction - Giovana M. Weckwerth; Thiago J. Dionísio; Yuri M. Costa; Bella L. Colombini-Ishiquiriama; Gabriela M. Oliveira; Elza A. Torres; Leonardo R. Bonjardim; Adriana M. Calvo; Troy Moore; Devin M. Absher; Carlos F. Santos (European Journal of Clinical Pharmacology, 2021)

Mud volcano possibly linked to seismogenic faults in the Kumano Basin, Nankai Trough, Japan - Miho Asada; Gregory F. Moore; Kiichiro Kawamura; Takuroh Noguchi (Marine Geophysical Research, 2021)

Vascular plant extinction in the continental United States and Canada - Wesley M. Knapp; Anne Frances; Reed Noss; Robert F. C. Naczi; Alan Weakley; George D. Gann; Bruce G. Baldwin; James Miller; Patrick McIntyre; Brent D. Mishler; Gerry Moore; Richard G. Olmstead; et al. (Conservation Biology, 2021)
Extinction rates are expected to increase during the Anthropocene. Current extinction rates of plants and many animals remain unknown. We quantified extinctions among the vascular flora of the continental United States and Canada since European settlement. We compiled data on apparently extinct species by querying plant conservation databases, searching the literature, and vetting the resulting list with botanical experts. Because taxonomic opinion varies widely, we developed an index of taxonomic uncertainty (ITU). The ITU ranges from A to F, with A indicating unanimous taxonomic recognition and F indicating taxonomic recognition by only a single author. The ITU allowed us to rigorously evaluate extinction rates. Our data suggest that 51 species and 14 infraspecific taxa, representing 33 families and 49 genera of vascular plants, have become extinct in our study area since European settlement. Seven of these taxa exist in cultivation but are extinct in the wild. Most extinctions occurred in the west, but this outcome may reflect the timing of botanical exploration relative to settlement. Sixty‐four percent of extinct plants were single‐site endemics, and many occurred outside recognized biodiversity hotspots. Given the paucity of plant surveys in many areas, particularly prior to European settlement, the actual extinction rate of vascular plants is undoubtedly much higher than indicated here.

Atmospheric pressure loading in GPS positions: dependency on GPS processing methods and effect on assessment of seasonal deformation in the contiguous USA and Alaska - Hilary R. Martens; Donald F. Argus; Cody Norberg; Geoffrey Blewitt; Thomas A. Herring; Angelyn W. Moore; William C. Hammond; Corné Kreemer (Journal of Geodesy, 2020)

Predicting biodiversity richness in rapidly changing landscapes: climate, low human pressure or protection as salvation? - David W. Macdonald; Luca Chiaverini; Helen M. Bothwell; Żaneta Kaszta; Eric Ash; Gilmoore Bolongon; Özgün Emre Can; Ahimsa Campos-Arceiz; Phan Channa; Gopalasamy Reuben Clements; Andrew J. Hearn; Laurie Hedges; et al. (Biodiversity and Conservation, 2020)
Rates of biodiversity loss in Southeast Asia are among the highest in the world, and the Indo-Burma and South-Central China Biodiversity Hotspots rank among the world’s most threatened. Developing robust multi-species conservation models is critical for stemming biodiversity loss both here and globally. We used a large and geographically extensive remote-camera survey and multi-scale, multivariate optimization species distribution modelling to investigate the factors driving biodiversity across these two adjoining biodiversity hotspots. Four major findings emerged from the work. (i) We identified clear spatial patterns of species richness, with two main biodiverse centres in the Thai-Malay Peninsula and in the mountainous region of Southwest China. (ii) Carnivores in particular, and large ungulates to a lesser degree, were the strongest indicators of species richness. (iii) Climate had the largest effect on biodiversity, followed by protected status and human footprint. (iv) Gap analysis between the biodiversity model and the current system of protected areas revealed that the majority of areas supporting the highest predicted biodiversity are not protected. Our results highlighted several key locations that should be prioritized for expanding the protected area network to maximize conservation effectiveness. We demonstrated the importance of switching from single-species to multi-species approaches to highlight areas of high priority for biodiversity conservation. In addition, since these areas mostly occur over multiple countries, we also advocate for a paradigmatic focus on transboundary conservation planning.

Global impacts of fertilization and herbivore removal on soil net nitrogen mineralization are modulated by local climate and soil properties - Anita C. Risch; Stefan Zimmermann; Barbara Moser; Martin Schütz; Frank Hagedorn; Jennifer Firn; Philip A. Fay; Peter B. Adler; Lori A. Biederman; John M. Blair; Elizabeth T. Borer; Arthur A. D. Broadbent; et al. (Global Change Biology, 2020)
Soil nitrogen (N) availability is critical for grassland functioning. However, human activities have increased the supply of biologically limiting nutrients, and changed the density and identity of mammalian herbivores. These anthropogenic changes may alter net soil N mineralization (soil net N min ), that is, the net balance between N mineralization and immobilization, which could severely impact grassland structure and functioning. Yet, to date, little is known about how fertilization and herbivore removal individually, or jointly, affect soil net N min across a wide range of grasslands that vary in soil and climatic properties. Here we collected data from 22 grasslands on five continents, all part of a globally replicated experiment, to assess how fertilization and herbivore removal affected potential (laboratory‐based) and realized (field‐based) soil net N min . Herbivore removal in the absence of fertilization did not alter potential and realized soil net N min . However, fertilization alone and in combination with herbivore removal consistently increased potential soil net N min. Realized soil net N min , in contrast, significantly decreased in fertilized plots where herbivores were removed. Treatment effects on potential and realized soil net N min were contingent on site‐specific soil and climatic properties. Fertilization effects on potential soil net N min were larger at sites with higher mean annual precipitation (MAP) and temperature of the wettest quarter (T.q.wet). Reciprocally, realized soil net N min declined most strongly with fertilization and herbivore removal at sites with lower MAP and higher T.q.wet. In summary, our findings show that anthropogenic nutrient enrichment, herbivore exclusion and alterations in future climatic conditions can negatively impact soil net N min across global grasslands under realistic field conditions. This is an important context‐dependent knowledge for grassland management worldwide.

Low Static Shear Modulus Along Foliation and Its Influence on the Elastic and Strength Anisotropy of Poorman Schist Rocks, Homestake Mine, South Dakota - Katherine J. Condon; Hiroki Sone; Herbert F. Wang; J. Ajo-Franklin; T. Baumgartner; K. Beckers; D. Blankenship; A. Bonneville; L. Boyd; S. Brown; J. A. Burghardt; C. Chai; et al. (Rock Mechanics and Rock Engineering, 2020)

Fear expression is reduced after acute and repeated nociceptin/orphanin FQ (NOP) receptor antagonism in rats: therapeutic implications for traumatic stress exposure - Rachel M. Taylor; Isaac H. Jeong; Matthew D. May; Elizabeth M. Bergman; Vincent F. Capaldi; Nicole L.T. Moore; Liana M. Matson; Emily G. Lowery-Gionta (Psychopharmacology, 2020)

Interactions among Triatoma sanguisuga blood feeding sources, gut microbiota and Trypanosoma cruzi diversity in southern Louisiana - Eric Dumonteil; Henry Pronovost; Eli F. Bierman; Anna Sanford; Alicia Majeau; Ryan Moore; Claudia Herrera (Molecular Ecology, 2020)
Integrating how biodiversity and infectious disease dynamics are linked at multiple levels and scales is highly challenging. Chagas disease is a vector‐borne disease, with specificities of the triatomine vectors and Trypanosoma cruzi parasite life histories resulting in a complex multihost and multistrain life cycle. Here, we tested the hypothesis that T. cruzi transmission cycles are shaped by triatomine host communities and gut microbiota composition by comparing the integrated interactions of Triatoma sanguisuga in southern Louisiana with feeding hosts, T. cruzi parasite and bacterial microbiota in two habitats. Bugs were collected from resident's houses and animal shelters and analysed for genetic structure, blood feeding sources, T. cruzi parasites, and bacterial diversity by PCR amplification of specific DNA markers followed by next‐generation sequencing, in an integrative metabarcoding approach. T. sanguisuga feeding host communities appeared opportunistic and defined by host abundance in each habitat, yielding distinct parasite transmission networks among hosts. The circulation of a large diversity of T. cruzi DTUs was also detected, with TcII and TcV detected for the first time in triatomines in the US. The bacterial microbiota was highly diverse and varied significantly according to the DTU infecting the bugs, indicating specific interactions among them in the gut. Expanding such studies to multiple habitats and additional triatomine species would be key to further refine our understanding of the complex life cycles of multihost, multistrain parasites such as T. cruzi , and may lead to improved disease control strategies.

Detection of the rare Australian endemic blind cave eel (Ophisternon candidum) with environmental DNA: implications for threatened species management in subterranean environments - Nicole E. White; Michelle T. Guzik; Andrew D. Austin; Glenn I. Moore; William F. Humphreys; Jason Alexander; Michael Bunce (Hydrobiologia, 2020)

Nutrient availability controls the impact of mammalian herbivores on soil carbon and nitrogen pools in grasslands - Judith Sitters; E. R. Jasper Wubs; Elisabeth S. Bakker; Thomas W. Crowther; Peter B. Adler; Sumanta Bagchi; Jonathan D. Bakker; Lori Biederman; Elizabeth T. Borer; Elsa E. Cleland; Nico Eisenhauer; Jennifer Firn; et al. (Global Change Biology, 2020)
Grasslands are subject to considerable alteration due to human activities globally, including widespread changes in populations and composition of large mammalian herbivores and elevated supply of nutrients. Grassland soils remain important reservoirs of carbon (C) and nitrogen (N). Herbivores may affect both C and N pools and these changes likely interact with increases in soil nutrient availability. Given the scale of grassland soil fluxes, such changes can have striking consequences for atmospheric C concentrations and the climate. Here, we use the Nutrient Network experiment to examine the responses of soil C and N pools to mammalian herbivore exclusion across 22 grasslands, under ambient and elevated nutrient availabilities (fertilized with NPK + micronutrients). We show that the impact of herbivore exclusion on soil C and N pools depends on fertilization. Under ambient nutrient conditions, we observed no effect of herbivore exclusion, but under elevated nutrient supply, pools are smaller upon herbivore exclusion. The highest mean soil C and N pools were found in grazed and fertilized plots. The decrease in soil C and N upon herbivore exclusion in combination with fertilization correlated with a decrease in aboveground plant biomass and microbial activity, indicating a reduced storage of organic matter and microbial residues as soil C and N. The response of soil C and N pools to herbivore exclusion was contingent on temperature – herbivores likely cause losses of C and N in colder sites and increases in warmer sites. Additionally, grasslands that contain mammalian herbivores have the potential to sequester more N under increased temperature variability and nutrient enrichment than ungrazed grasslands. Our study highlights the importance of conserving mammalian herbivore populations in grasslands worldwide. We need to incorporate local‐scale herbivory, and its interaction with nutrient enrichment and climate, within global‐scale models to better predict land–atmosphere interactions under future climate change.

Invasive non‐native species likely to threaten biodiversity and ecosystems in the Antarctic Peninsula region - Kevin A. Hughes; Oliver L. Pescott; Jodey Peyton; Tim Adriaens; Elizabeth J. Cottier‐Cook; Gillian Key; Wolfgang Rabitsch; Elena Tricarico; David K. A. Barnes; Naomi Baxter; Mark Belchier; Denise Blake; et al. (Global Change Biology, 2020)
The Antarctic is considered to be a pristine environment relative to other regions of the Earth, but it is increasingly vulnerable to invasions by marine, freshwater and terrestrial non‐native species. The Antarctic Peninsula region (APR), which encompasses the Antarctic Peninsula, South Shetland Islands and South Orkney Islands, is by far the most invaded part of the Antarctica continent. The risk of introduction of invasive non‐native species to the APR is likely to increase with predicted increases in the intensity, diversity and distribution of human activities. Parties that are signatories to the Antarctic Treaty have called for regional assessments of non‐native species risk. In response, taxonomic and Antarctic experts undertook a horizon scanning exercise using expert opinion and consensus approaches to identify the species that are likely to present the highest risk to biodiversity and ecosystems within the APR over the next 10 years. One hundred and three species, currently absent in the APR, were identified as relevant for review, with 13 species identified as presenting a high risk of invading the APR. Marine invertebrates dominated the list of highest risk species, with flowering plants and terrestrial invertebrates also represented; however, vertebrate species were thought unlikely to establish in the APR within the 10 year timeframe. We recommend (a) the further development and application of biosecurity measures by all stakeholders active in the APR, including surveillance for species such as those identified during this horizon scanning exercise, and (b) use of this methodology across the other regions of Antarctica. Without the application of appropriate biosecurity measures, rates of introductions and invasions within the APR are likely to increase, resulting in negative consequences for the biodiversity of the whole continent, as introduced species establish and spread further due to climate change and increasing human activity.

Global Wildland Fire Management Research Needs - Peter F. Moore (Current Forestry Reports, 2019)

Belowground Biomass Response to Nutrient Enrichment Depends on Light Limitation Across Globally Distributed Grasslands - Elsa E. Cleland; Eric M. Lind; Nicole M. DeCrappeo; Elizabeth DeLorenze; Rachel Abbott Wilkins; Peter B. Adler; Jonathan D. Bakker; Cynthia S. Brown; Kendi F. Davies; Ellen Esch; Jennifer Firn; Scott Gressard; et al. (Ecosystems, 2019)

A Mechanical Brain Damage Framework Used to Model Abnormal Brain Tau Protein Accumulations of National Football League Players - M. F. Horstemeyer; P. R. Berthelson; J. Moore; A. K. Persons; A. Dobbins; R. K. Prabhu (Annals of Biomedical Engineering, 2019)

Antibiotic misuse in respiratory tract infections in children and adults—a prospective, multicentre study (TAILORED Treatment) - Chantal B. van Houten; Asi Cohen; Dan Engelhard; John P. Hays; Roger Karlsson; Edward Moore; David Fernández; Racheli Kreisberg; Laurence V. Collins; Wouter de Waal; Karin M. de Winter-de Groot; Tom F. W. Wolfs; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Male parental investment reflects the level of partner contributions and brood value in tree swallows - Ádám Z. Lendvai; Çağlar Akçay; Mark Stanback; Mark F. Haussmann; Ignacio T. Moore; Frances Bonier (Behavioral Ecology and Sociobiology, 2018)

Temporal thermal refugia and seasonal variation in upper thermal limits of two species of riverine invertebrates: the amphipod, Paramelita nigroculus, and the mayfly, Lestagella penicillata - Helen F. Dallas; Nicholas A. Rivers-Moore (Aquatic Ecology, 2018)

Relationships between agroforestry and community development according to practitioners - John F. Munsell; Benjamin J. Addlestone; Catherine J. Bukowski; Louis Nkembi; Neba Kingsly; Elizabeth A. Moore (Agroforestry Systems, 2018)

Interaction between known risk factors for head and neck cancer and socioeconomic status: the Carolina Head and Neck Cancer Study - Gaelen Stanford-Moore; Patrick T. Bradshaw; Mark C. Weissler; Jose P. Zevallos; Paul Brennan; Devasena Anantharaman; Behnoush Abedi-Ardekani; Andrew F. Olshan (Cancer Causes & Control, 2018)

Climate research priorities for policy-makers, practitioners, and scientists in Georgia, USA - Murray A. Rudd; Althea F. P. Moore; Daniel Rochberg; Lisa Bianchi-Fossati; Marilyn A. Brown; David D’Onofrio; Carrie A. Furman; Jairo Garcia; Ben Jordan; Jennifer Kline; L. Mark Risse; Patricia L. Yager; et al. (Environmental Management, 2018)

Genomes of ubiquitous marine and hypersaline Hydrogenovibrio , Thiomicrorhabdus and Thiomicrospira spp. encode a diversity of mechanisms to sustain chemolithoautotrophy in heterogeneous environments - Kathleen M. Scott; John Williams; Cody M. B. Porter; Sydney Russel; Tara L. Harmer; John H. Paul; Kirsten M. Antonen; Megan K. Bridges; Gary J. Camper; Christie K. Campla; Leila G. Casella; Eva Chase; et al. (Environmental Microbiology, 2018)
Summary Chemolithoautotrophic bacteria from the genera Hydrogenovibrio, Thiomicrorhabdus and Thiomicrospira are common, sometimes dominant, isolates from sulfidic habitats including hydrothermal vents, soda and salt lakes and marine sediments. Their genome sequences confirm their membership in a deeply branching clade of the Gammaproteobacteria . Several adaptations to heterogeneous habitats are apparent. Their genomes include large numbers of genes for sensing and responding to their environment (EAL‐ and GGDEF‐domain proteins and methyl‐accepting chemotaxis proteins) despite their small sizes (2.1–3.1 Mbp). An array of sulfur‐oxidizing complexes are encoded, likely to facilitate these organisms' use of multiple forms of reduced sulfur as electron donors. Hydrogenase genes are present in some taxa, including group 1d and 2b hydrogenases in Hydrogenovibrio marinus and H. thermophilus MA2‐6, acquired via horizontal gene transfer. In addition to high‐affinity cbb 3 cytochrome c oxidase, some also encode cytochrome bd‐ type quinol oxidase or ba 3 ‐ type cytochrome c oxidase, which could facilitate growth under different oxygen tensions, or maintain redox balance. Carboxysome operons are present in most, with genes downstream encoding transporters from four evolutionarily distinct families, which may act with the carboxysomes to form CO 2 concentrating mechanisms. These adaptations to habitat variability likely contribute to the cosmopolitan distribution of these organisms.

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Leveraging epigenomics and contactomics data to investigate SNP pairs in GWAS - Elisabetta Manduchi; Scott M. Williams; Alessandra Chesi; Matthew E. Johnson; Andrew D. Wells; Struan F. A. Grant; Jason H. Moore (Human Genetics, 2018)

Bathymetric imaging of protothrust zone along the Nankai Trough - Mikiya Yamashita; Seiichi Miura; Gregory F. Moore; Ayako Nakanishi; Shuichi Kodaira; Yoshiyuki Kaneda (Island Arc, 2018)

Assessing uncertainties in crop and pasture ensemble model simulations of productivity and N 2 O emissions - Fiona Ehrhardt; Jean‐François Soussana; Gianni Bellocchi; Peter Grace; Russel McAuliffe; Sylvie Recous; Renáta Sándor; Pete Smith; Val Snow; Massimiliano de Antoni Migliorati; Bruno Basso; Arti Bhatia; et al. (Global Change Biology, 2018)
Simulation models are extensively used to predict agricultural productivity and greenhouse gas emissions. However, the uncertainties of (reduced) model ensemble simulations have not been assessed systematically for variables affecting food security and climate change mitigation, within multi‐species agricultural contexts. We report an international model comparison and benchmarking exercise, showing the potential of multi‐model ensembles to predict productivity and nitrous oxide (N 2 O) emissions for wheat, maize, rice and temperate grasslands. Using a multi‐stage modelling protocol, from blind simulations (stage 1) to partial (stages 2–4) and full calibration (stage 5), 24 process‐based biogeochemical models were assessed individually or as an ensemble against long‐term experimental data from four temperate grassland and five arable crop rotation sites spanning four continents. Comparisons were performed by reference to the experimental uncertainties of observed yields and N 2 O emissions. Results showed that across sites and crop/grassland types, 23%–40% of the uncalibrated individual models were within two standard deviations ( SD ) of observed yields, while 42 (rice) to 96% (grasslands) of the models were within 1 SD of observed N 2 O emissions. At stage 1, ensembles formed by the three lowest prediction model errors predicted both yields and N 2 O emissions within experimental uncertainties for 44% and 33% of the crop and grassland growth cycles, respectively. Partial model calibration (stages 2–4) markedly reduced prediction errors of the full model ensemble E‐median for crop grain yields (from 36% at stage 1 down to 4% on average) and grassland productivity (from 44% to 27%) and to a lesser and more variable extent for N 2 O emissions. Yield‐scaled N 2 O emissions (N 2 O emissions divided by crop yields) were ranked accurately by three‐model ensembles across crop species and field sites. The potential of using process‐based model ensembles to predict jointly productivity and N 2 O emissions at field scale is discussed.

Energy conserving thermoregulatory patterns and lower disease severity in a bat resistant to the impacts of white-nose syndrome - Marianne S. Moore; Kenneth A. Field; Melissa J. Behr; Gregory G. Turner; Morgan E. Furze; Daniel W. F. Stern; Paul R. Allegra; Sarah A. Bouboulis; Chelsey D. Musante; Megan E. Vodzak; Matthew E. Biron; Melissa B. Meierhofer; et al. (Journal of Comparative Physiology B, 2018)

Sex matters in massive parallel sequencing: Evidence for biases in genetic parameter estimation and investigation of sex determination systems - Laura Benestan; Jean‐Sébastien Moore; Ben J. G. Sutherland; Jérémy Le Luyer; Halim Maaroufi; Clément Rougeux; Eric Normandeau; Nathan Rycroft; Jelle Atema; Les N. Harris; Ross F. Tallman; Spencer J. Greenwood; et al. (Molecular Ecology, 2017)
Using massively parallel sequencing data from two species with different life history traits, American lobster ( Homarus americanus ) and Arctic Char ( Salvelinus alpinus ), we highlight how an unbalanced sex ratio in the samples and a few sex‐linked markers may lead to false interpretations of population structure and thus to potentially erroneous management recommendations. Here, multivariate analyses revealed two genetic clusters separating samples by sex instead of by expected spatial variation: inshore and offshore locations in lobster, or east and west locations in Arctic Char. To further investigate this, we created several subsamples artificially varying the sex ratio in the inshore/offshore and east/west groups and then demonstrated that significant genetic differentiation could be observed despite panmixia in lobster, and that F ST values were overestimated in Arctic Char. This pattern was due to 12 and 94 sex‐linked markers driving differentiation for lobster and Arctic Char, respectively. Removing sex‐linked markers led to nonsignificant genetic structure in lobster and a more accurate estimation of F ST in Arctic Char. The locations of these markers and putative identities of genes containing or nearby the markers were determined using available transcriptomic and genomic data, and this provided new information related to sex determination in both species. Given that only 9.6% of all marine/diadromous population genomic studies to date have reported sex information, we urge researchers to collect and consider individual sex information. Sex information is therefore relevant for avoiding unexpected biases due to sex‐linked markers as well as for improving our knowledge of sex determination systems in nonmodel species.

Genomics and telemetry suggest a role for migration harshness in determining overwintering habitat choice, but not gene flow, in anadromous Arctic Char - Jean‐Sébastien Moore; Les N. Harris; Jérémy Le Luyer; Ben J.G. Sutherland; Quentin Rougemont; Ross F. Tallman; Aaron T. Fisk; Louis Bernatchez (Molecular Ecology, 2017)
Migration is a ubiquitous life history trait with profound evolutionary and ecological consequences. Recent developments in telemetry and genomics, when combined, can bring significant insights on the migratory ecology of nonmodel organisms in the wild. Here, we used this integrative approach to document dispersal, gene flow and potential for local adaptation in anadromous Arctic Char from six rivers in the Canadian Arctic. Acoustic telemetry data from 124 tracked individuals indicated asymmetric dispersal, with a large proportion of fish (72%) tagged in three different rivers migrating up the same short river in the fall. Population genomics data from 6,136 SNP markers revealed weak, albeit significant, population differentiation (average pairwise F ST = 0.011) and asymmetric dispersal was also revealed by population assignments. Approximate Bayesian computation simulations suggested the presence of asymmetric gene flow, although in the opposite direction to that observed from the telemetry data, suggesting that dispersal does not necessarily lead to gene flow. These observations suggested that Arctic Char home to their natal river to spawn, but may overwinter in rivers with the shortest migratory route to minimize the costs of migration in nonbreeding years. Genome scans and genetic–environment associations identified 90 outlier markers putatively under selection, 23 of which were in or near a gene. Of these, at least four were involved in muscle and cardiac function, consistent with the hypothesis that migratory harshness could drive local adaptation. Our study illustrates the power of integrating genomics and telemetry to study migrations in nonmodel organisms in logistically challenging environments such as the Arctic.

Case-crossover analysis of heat-coded deaths and vulnerable subpopulations: Oklahoma, 1990–2011 - Brianna F. Moore; G. Brooke Anderson; Matthew G. Johnson; Sheryll Brown; Kristy K. Bradley; Sheryl Magzamen (International Journal of Biometeorology, 2017)

Piscirickettsia salmonis infection in cultured lumpfish ( Cyclopterus lumpus L.) - M Marcos‐López; N M Ruane; F Scholz; M Bolton‐Warberg; S O Mitchell; S Murphy O'Sullivan; A Irwin Moore; H D Rodger (Journal of Fish Diseases, 2017)
A Piscirickettsia salmonis infection was diagnosed in lumpfish ( Cyclopterus lumpus L.) juveniles held in a marine research facility on the west coast of Ireland. The main clinical signs and pathology included marked ascites, severe multifocal liver necrosis and severe diffuse inflammation and necrosis of the exocrine pancreas and peri‐pancreatic adipose tissue. Numerous Piscirickettsia ‐like organisms were observed by histopathology in the affected organs, and the bacterial species was characterized by molecular analysis. Sequencing of the partial 16S rDNA gene and internal transcribed spacer region showed the lumpfish sequences to be closely related to previously identified Atlantic salmon ( Salmo salar L.) sequences from Ireland. To the authors’ knowledge, this is the first detection of P. salmonis in lumpfish worldwide. The infection is considered potentially significant in terms of lumpfish health and biosecurity.

Evaluating a polyculture trap crop for organic management of Halyomorpha halys and native stink bugs in peppers - Clarissa R. Mathews; Brett Blaauw; Galen Dively; James Kotcon; Jennifer Moore; Emily Ogburn; Douglas G. Pfeiffer; Taliaferro Trope; James F. Walgenbach; Celeste Welty; Gladis Zinati; Anne L. Nielsen (Journal of Pest Science, 2017)

The Asia-Pacific’s role in the emerging solar geoengineering debate - Masahiro Sugiyama; Shinichiro Asayama; Atsushi Ishii; Takanobu Kosugi; John C. Moore; Jolene Lin; Penehuro F. Lefale; Wil Burns; Masatomo Fujiwara; Arunabha Ghosh; Joshua Horton; Atsushi Kurosawa; et al. (Climatic Change, 2017)

Internal deformation of a muddy gravity flow and its interaction with the seafloor (site C0018 of IODP Expedition 333, Nankai Trough, SE Japan) - J. S. Laberg; M. Strasser; T. M. Alves; S. Gao; K. Kawamura; A. Kopf; G. F. Moore (Landslides, 2017)

Peptide-binding motifs of two common equine class I MHC molecules in Thoroughbred horses - Tobias Bergmann; Mikaela Lindvall; Erin Moore; Eugene Moore; John Sidney; Donald Miller; Rebecca L. Tallmadge; Paisley T. Myers; Stacy A. Malaker; Jeffrey Shabanowitz; Nikolaus Osterrieder; Bjoern Peters; et al. (Immunogenetics, 2017)

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

Overlapping life-history stages in migrating songbirds: variation in circulating testosterone and testosterone production capacity - Kristen M. Covino; Jodie M. Jawor; Jeffrey F. Kelly; Frank R. Moore (Journal of Ornithology, 2017)

Optimizing control programmes by integrating data from fine-scale space use by introduced predators - Mariano R. Recio; Richard F. Maloney; Renaud Mathieu; Emilio Virgós; Antoni B. Moore; Philip J. Seddon (Biological Invasions, 2017)

Changes in resting mitogen-activated protein kinases following resistance exercise overreaching and overtraining - Justin X. Nicoll; Andrew C. Fry; Andrew J. Galpin; Adam J. Sterczala; Donald B. Thomason; Christopher A. Moore; Lawrence W. Weiss; Loren Z. F. Chiu (European Journal of Applied Physiology, 2016)

Towards using thermal stress thresholds to predict salmonid invasion potential - Bruce R. Ellender; Nick A. Rivers-Moore; Christine R. Coppinger; Terence A. Bellingan; Olaf L. F. Weyl (Biological Invasions, 2016)

Entomopathogenic fungi as control agents of Thaumatotibia leucotreta in citrus orchards: field efficacy and persistence - C. A. Coombes; M. P. Hill; S. D. Moore; J. F. Dames (BioControl, 2016)

Antibiotics as CECs: An Overview of the Hazards Posed by Antibiotics and Antibiotic Resistance - Geoffrey I. Scott; Dwayne E. Porter; R. Sean Norman; C. Hart Scott; Miguel I. Uyaguari-Diaz; Keith A. Maruya; Steve B. Weisberg; Michael H. Fulton; Ed F. Wirth; Janet Moore; Paul L. Pennington; Daniel Schlenk; et al. (Frontiers in Marine Science, 2016)

Rock geochemistry induces stress and starvation responses in the bacterial proteome - Casey C. Bryce; Thierry Le Bihan; Sarah F. Martin; Jesse P. Harrison; Timothy Bush; Bryan Spears; Alanna Moore; Natalie Leys; Bo Byloos; Charles S. Cockell (Environmental Microbiology, 2016)
Summary Interactions between microorganisms and rocks play an important role in Earth system processes. However, little is known about the molecular capabilities microorganisms require to live in rocky environments. Using a quantitative label‐free proteomics approach, we show that a model bacterium ( C upriavidus metallidurans CH 34) can use volcanic rock to satisfy some elemental requirements, resulting in increased rates of cell division in both magnesium‐ and iron‐limited media. However, the rocks also introduced multiple new stresses via chemical changes associated with pH , elemental leaching and surface adsorption of nutrients that were reflected in the proteome. For example, the loss of bioavailable phosphorus was observed and resulted in the upregulation of diverse phosphate limitation proteins, which facilitate increase phosphate uptake and scavenging within the cell. Our results revealed that despite the provision of essential elements, rock chemistry drives complex metabolic reorganization within rock‐dwelling organisms, requiring tight regulation of cellular processes at the protein level. This study advances our ability to identify key microbial responses that enable life to persist in rock environments.

Characterization of the peptide binding specificity of the HLA class I alleles B*38:01 and B*39:06 - John Sidney; Jennifer Schloss; Carrie Moore; Mikaela Lindvall; Amanda Wriston; Donald F. Hunt; Jeffrey Shabanowitz; Teresa P. DiLorenzo; Alessandro Sette (Immunogenetics, 2016)

Refinement of the canine CD1 locus topology and investigation of antibody binding to recombinant canine CD1 isoforms - Mette Schjaerff; Stefan M. Keller; Joseph Fass; Lutz Froenicke; Robert A. Grahn; Leslie Lyons; Verena K. Affolter; Annemarie T. Kristensen; Peter F. Moore (Immunogenetics, 2016)

Hypovolemic men and women regulate blood pressure differently following exposure to artificial gravity - Joyce M. Evans; L. Christine Ribeiro; Fritz B. Moore; Siqi Wang; Qingguang Zhang; Vladimir Kostas; Connor R. Ferguson; Jorge Serrador; Michael Falvo; Michael B. Stenger; Nandu Goswami; Jon C. Rask; et al. (European Journal of Applied Physiology, 2015)

Coastal Vertebrate Exposure to Predicted Habitat Changes Due to Sea Level Rise - Elizabeth A. Hunter; Nathan P. Nibbelink; Clark R. Alexander; Kyle Barrett; Lara F. Mengak; Rachel K. Guy; Clinton T. Moore; Robert J. Cooper (Environmental Management, 2015)

The common equine class I molecule Eqca-1*00101 (ELA-A3.1) is characterized by narrow peptide binding and T cell epitope repertoires - Tobias Bergmann; Carrie Moore; John Sidney; Donald Miller; Rebecca Tallmadge; Rebecca M. Harman; Carla Oseroff; Amanda Wriston; Jeffrey Shabanowitz; Donald F. Hunt; Nikolaus Osterrieder; Bjoern Peters; et al. (Immunogenetics, 2015)

Potential Health Risk of Herbal Distillates and Decoctions Consumption in Shiraz, Iran - F. Moore; R. Akhbarizadeh; B. Keshavarzi; F. Tavakoli (Biological Trace Element Research, 2015)

Modernizing Pharmaceutical Manufacturing: from Batch to Continuous Production - Sau L. Lee; Thomas F. O’Connor; Xiaochuan Yang; Celia N. Cruz; Sharmista Chatterjee; Rapti D. Madurawe; Christine M. V. Moore; Lawrence X. Yu; Janet Woodcock (Journal of Pharmaceutical Innovation, 2015)

Microneedle characterisation: the need for universal acceptance criteria and GMP specifications when moving towards commercialisation - Rebecca E. M. Lutton; Jessica Moore; Eneko Larrañeta; Stephen Ligett; A. David Woolfson; Ryan F. Donnelly (Drug Delivery and Translational Research, 2015)

Using SWAT for sub-field identification of phosphorus critical source areas in a saturation excess runoff region - Michael F. Winchell; Solomon Folle; Donald Meals; Julie Moore; Raghavan Srinivasan; Eric A. Howe (Hydrological Sciences Journal, 2015)

Ecotoxicological risk of polycyclic aromatic hydrocarbons (PAHs) in urban soil of Isfahan metropolis, Iran - F. Moore; R. Akhbarizadeh; B. Keshavarzi; S. Khabazi; A. Lahijanzadeh; M. Kermani (Environmental Monitoring and Assessment, 2015)

Identifying best methods for routine ELISA detection of microcystin in seafood - Ellen P. Preece; Barry C. Moore; Mark E. Swanson; F. Joan Hardy (Environmental Monitoring and Assessment, 2015)

Recognition of a highly restricted freshwater snail lineage (Physidae: Physella) in southeastern Oregon: convergent evolution, historical context, and conservation considerations - Alexandria C. Moore; John B. Burch; Thomas F. Duda (Conservation Genetics, 2015)

Heavy metals fractionation in surface sediments of Gowatr bay-Iran - F. Moore; M. J. Nematollahi; B. Keshavarzi (Environmental Monitoring and Assessment, 2015)

Strengthening confidence in climate change impact science - Mary I. O'Connor; Johnna M. Holding; Carrie V. Kappel; Carlos M. Duarte; Keith Brander; Christopher J. Brown; John F. Bruno; Lauren Buckley; Michael T. Burrows; Benjamin S. Halpern; Wolfgang Kiessling; Pippa Moore; et al. (Global Ecology and Biogeography, 2015)
Aim To assess confidence in conclusions about climate‐driven biological change through time, and identify approaches for strengthening confidence scientific conclusions about ecological impacts of climate change. Location Global. Methods We outlined a framework for strengthening confidence in inferences drawn from biological climate impact studies through the systematic integration of prior expectations, long‐term data and quantitative statistical procedures. We then developed a numerical confidence index ( C index ) and used it to evaluate current practices in 208 studies of marine climate impacts comprising 1735 biological time series. Results Confidence scores for inferred climate impacts varied widely from 1 to 16 (very low to high confidence). Approximately 35% of analyses were not associated with clearly stated prior expectations and 65% of analyses did not test putative non‐climate drivers of biological change. Among the highest‐scoring studies, 91% tested prior expectations, 86% formulated expectations for alternative drivers but only 63% statistically tested them. Higher confidence scores observed in studies that did not detect a change or tracked multiple species suggest publication bias favouring impact studies that are consistent with climate change. The number of time series showing climate impacts was a poor predictor of average confidence scores for a given group, reinforcing that vote‐counting methodology is not appropriate for determining overall confidence in inferences. Main conclusions Climate impacts research is expected to attribute biological change to climate change with measurable confidence. Studies with long‐term, high‐resolution data, appropriate statistics and tests of alternative drivers earn higher C index scores, suggesting these should be given greater weight in impact assessments. Together with our proposed framework, the results of our C index analysis indicate how the science of detecting and attributing biological impacts to climate change can be strengthened through the use of evidence‐based prior expectations and thorough statistical analyses, even when data are limited, maximizing the impact of the diverse and growing climate change ecology literature.

Mapping migration in a songbird using high‐resolution genetic markers - Kristen C. Ruegg; Eric C. Anderson; Kristina L. Paxton; Vanessa Apkenas; Sirena Lao; Rodney B. Siegel; David F. DeSante; Frank Moore; Thomas B. Smith (Molecular Ecology, 2014)
Neotropic migratory birds are declining across the W estern H emisphere, but conservation efforts have been hampered by the inability to assess where migrants are most limited—the breeding grounds, migratory stopover sites or wintering areas. A major challenge has been the lack of an efficient, reliable and broadly applicable method for measuring the strength of migratory connections between populations across the annual cycle. Here, we show how high‐resolution genetic markers can be used to identify genetically distinct groups of a migratory bird, the W ilson's warbler ( C ardellina pusilla ), at fine enough spatial scales to facilitate assessing regional drivers of demographic trends. By screening 1626 samples using 96 highly divergent single nucleotide polymorphisms selected from a large pool of candidates (~450 000), we identify novel region‐specific migratory routes and timetables of migration along the P acific F lyway. Our results illustrate that high‐resolution genetic markers are more reliable, precise and amenable to high throughput screening than previously described intrinsic marking techniques, making them broadly applicable to large‐scale monitoring and conservation of migratory organisms.

Linking Indices for Biodiversity Monitoring to Extinction Risk Theory - MICHAEL A. MCCARTHY; ALANA L. MOORE; JOCHEN KRAUSS; JOHN W. MORGAN; CHRISTOPHER F. CLEMENTS (Conservation Biology, 2014)
Biodiversity indices often combine data from different species when used in monitoring programs. Heuristic properties can suggest preferred indices, but we lack objective ways to discriminate between indices with similar heuristics. Biodiversity indices can be evaluated by determining how well they reflect management objectives that a monitoring program aims to support. For example, the Convention on Biological Diversity requires reporting about extinction rates, so simple indices that reflect extinction risk would be valuable. We developed 3 biodiversity indices that are based on simple models of population viability that relate extinction risk to abundance. We based the first index on the geometric mean abundance of species and the second on a more general power mean. In a third index, we integrated the geometric mean abundance and trend. These indices require the same data as previous indices, but they also relate directly to extinction risk. Field data for butterflies and woodland plants and experimental studies of protozoan communities show that the indices correlate with local extinction rates. Applying the index based on the geometric mean to global data on changes in avian abundance suggested that the average extinction probability of birds has increased approximately 1% from 1970 to 2009. Conectando Índices para el Monitoreo de la Biodiversidad con la Teoría de Riesgo de Extinción

Geographic influences on fine-scale, hierarchical population structure in northern Canadian populations of anadromous Arctic Char (Salvelinus alpinus) - Les N. Harris; Jean-Sébastien Moore; Paul Galpern; Ross F. Tallman; Eric B. Taylor (Environmental Biology of Fishes, 2014)

Erratum to: Agroforestry preferences in refugee hosting communities in Cameroon - Elizabeth A. Moore; John F. Munsell; A. L. Tom Hammett; Keith M. Moore (Agroforestry Systems, 2014)

Agroforestry preferences in refugee hosting communities in Cameroon - Elizabeth A. Moore; John F. Munsell; A. L. Tom Hammett; Keith M. Moore (Agroforestry Systems, 2014)

Distribution and diversity of V errucomicrobia methanotrophs in geothermal and acidic environments - Christine E. Sharp; Angela V. Smirnova; Jaime M. Graham; Matthew B. Stott; Roshan Khadka; Tim R. Moore; Stephen E. Grasby; Maria Strack; Peter F. Dunfield (Environmental Microbiology, 2014)
Summary Recently, methanotrophic members of the phylum V errucomicrobia have been described, but little is known about their distribution in nature. We surveyed methanotrophic bacteria in geothermal springs and acidic wetlands via pyrosequencing of 16 S rRNA gene amplicons. Putative methanotrophic V errucomicrobia were found in samples covering a broad temperature range (22.5–81.6° C ), but only in acidic conditions ( pH 1.8–5.0) and only in geothermal environments, not in acidic bogs or fens. Phylogenetically, three 16 S rRNA gene sequence clusters of putative methanotrophic V errucomicrobia were observed. Those detected in high‐temperature geothermal samples (44.1–81.6° C ) grouped with known thermoacidiphilic ‘ M ethylacidiphilum ’ isolates. A second group dominated in moderate‐temperature geothermal samples (22.5–40.1° C ) and a representative mesophilic methanotroph from this group was isolated (strain LP 2 A ). Genome sequencing verified that strain LP 2 A possessed particulate methane monooxygenase, but its 16 S rRNA gene sequence identity to ‘ M ethylacidiphilum infernorum ’ strain V4 was only 90.6%. A third group clustered distantly with known methanotrophic V errucomicrobia . Using pmoA ‐gene targeted quantitative polymerase chain reaction, two geothermal soil profiles showed a dominance of LP 2 A ‐like pmoA sequences in the cooler surface layers and ‘ M ethylacidiphilum'‐ like pmoA sequences in deeper, hotter layers. Based on these results, there appears to be a thermophilic group and a mesophilic group of methanotrophic V errucomicrobia . However, both were detected only in acidic geothermal environments.

Sex differences in the effect of wheel running on subsequent nicotine-seeking in a rat adolescent-onset self-administration model - Victoria Sanchez; Catherine F. Moore; Darlene H. Brunzell; Wendy J. Lynch (Psychopharmacology, 2014)

Mark recapture estimates of dispersal ability and observations on the territorial behaviour of the rare hoverfly, Hammerschmidtia ferruginea (Diptera, Syrphidae) - E. L. Rotheray; L. F. Bussière; Pete Moore; Linnea Bergstrom; D. Goulson (Journal of Insect Conservation, 2014)

Genetic analysis of sympatric migratory ecotypes of Arctic charr Salvelinus alpinus : alternative mating tactics or reproductively isolated strategies? - J.‐S. Moore; T. N. Loewen; L. N. Harris; R. F. Tallman (Journal of Fish Biology, 2014)
Three populations of Arctic charr Salvelinus alpinus from southern Baffin Island were previously identified to display variable migratory phenotypes, with an anadromous component of the population and another remaining resident in fresh water. In this study, 14 microsatellite markers were used to help distinguish between two alternative hypotheses to explain the co‐existence of the two ecotypes: that the two ecotypes originate from a single population and are the result of a conditional mating tactic or that the migratory ecotypes are reproductively isolated populations utilizing alternative migratory strategies. In two of the three replicate systems, F ST values between the resident and anadromous individuals were non‐significant, while they were significant in a third sampling location. Bayesian clustering analysis implemented in structure, however, failed to identify any within‐location clustering in all three sampling locations. It is concluded from these analyses that the life‐history ecotypes are most likely conditional mating tactics, rather than reproductively isolated populations. Other evidence in favour of the alternative mating tactic hypothesis is briefly reviewed, and implications for management of those populations are discussed.

Effect of wheel-running during abstinence on subsequent nicotine-seeking in rats - Victoria Sanchez; Catherine F. Moore; Darlene H. Brunzell; Wendy J. Lynch (Psychopharmacology, 2013)

Radon in indoor concentrations and indoor concentrations of metal dust particles in museums and other public buildings - G. L. Carneiro; D. Braz; E. F. de Jesus; S. M. Santos; K. Cardoso; A. A. Hecht; Moore K. Dias da Cunha (Environmental Geochemistry and Health, 2013)

Evaluation of potentially toxic metals pollution in the sediments of the Kor river, southwest Iran - V. Sheykhi; F. Moore (Environmental Monitoring and Assessment, 2013)

Assessing the Risk of Ships Striking Large Whales in Marine Spatial Planning - J. V. REDFERN; M. F. MCKENNA; T. J. MOORE; J. CALAMBOKIDIS; M. L. DEANGELIS; E. A. BECKER; J. BARLOW; K. A. FORNEY; P. C. FIEDLER; S. J. CHIVERS (Conservation Biology, 2013)
Marine spatial planning provides a comprehensive framework for managing multiple uses of the marine environment and has the potential to minimize environmental impacts and reduce conflicts among users. Spatially explicit assessments of the risks to key marine species from human activities are a requirement of marine spatial planning. We assessed the risk of ships striking humpback (Megaptera novaeangliae), blue (Balaenoptera musculus), and fin (Balaenoptera physalus) whales in alternative shipping routes derived from patterns of shipping traffic off Southern California (U.S.A.). Specifically, we developed whale‐habitat models and assumed ship‐strike risk for the alternative shipping routes was proportional to the number of whales predicted by the models to occur within each route. This definition of risk assumes all ships travel within a single route. We also calculated risk assuming ships travel via multiple routes. We estimated the potential for conflict between shipping and other uses (military training and fishing) due to overlap with the routes. We also estimated the overlap between shipping routes and protected areas. The route with the lowest risk for humpback whales had the highest risk for fin whales and vice versa. Risk to both species may be ameliorated by creating a new route south of the northern Channel Islands and spreading traffic between this new route and the existing route in the Santa Barbara Channel. Creating a longer route may reduce the overlap between shipping and other uses by concentrating shipping traffic. Blue whales are distributed more evenly across our study area than humpback and fin whales; thus, risk could not be ameliorated by concentrating shipping traffic in any of the routes we considered. Reducing ship‐strike risk for blue whales may be necessary because our estimate of the potential number of strikes suggests that they are likely to exceed allowable levels of anthropogenic impacts established under U.S. laws. Evaluación del Riesgo de Colisiones de Barcos y Ballenas en la Planificación Marina Espacial

Assessment of Management to Mitigate Anthropogenic Effects on Large Whales - JULIE M. VAN DER HOOP; MICHAEL J. MOORE; SUSAN G. BARCO; TIMOTHY V.N. COLE; PIERRE‐YVES DAOUST; ALLISON G. HENRY; DONALD F. MCALPINE; WILLIAM A. MCLELLAN; TONYA WIMMER; ANDREW R. SOLOW (Conservation Biology, 2013)
United States and Canadian governments have responded to legal requirements to reduce human‐induced whale mortality via vessel strikes and entanglement in fishing gear by implementing a suite of regulatory actions. We analyzed the spatial and temporal patterns of mortality of large whales in the Northwest Atlantic (23.5°N to 48.0°N), 1970 through 2009, in the context of management changes. We used a multinomial logistic model fitted by maximum likelihood to detect trends in cause‐specific mortalities with time. We compared the number of human‐caused mortalities with U.S. federally established levels of potential biological removal (i.e., species‐specific sustainable human‐caused mortality). From 1970 through 2009, 1762 mortalities (all known) and serious injuries (likely fatal) involved 8 species of large whales. We determined cause of death for 43% of all mortalities; of those, 67% (502) resulted from human interactions. Entanglement in fishing gear was the primary cause of death across all species (n = 323), followed by natural causes (n = 248) and vessel strikes (n = 171). Established sustainable levels of mortality were consistently exceeded in 2 species by up to 650%. Probabilities of entanglement and vessel‐strike mortality increased significantly from 1990 through 2009. There was no significant change in the local intensity of all or vessel‐strike mortalities before and after 2003, the year after which numerous mitigation efforts were enacted. So far, regulatory efforts have not reduced the lethal effects of human activities to large whales on a population‐range basis, although we do not exclude the possibility of success of targeted measures for specific local habitats that were not within the resolution of our analyses. It is unclear how shortfalls in management design or compliance relate to our findings. Analyses such as the one we conducted are crucial in critically evaluating wildlife‐management decisions. The results of these analyses can provide managers with direction for modifying regulated measures and can be applied globally to mortality‐driven conservation issues . Evaluación del Manejo para Mitigar Efectos Antropogénicos sobre Ballenas Mayores

Young research investigators honored at the 2012 Gordon Research Conference on photosynthesis - Gary F. Moore; Gennady M. Ananyev; Govindjee (Photosynthesis Research, 2012)

The mammalian gene function resource: the international knockout mouse consortium - Allan Bradley; Konstantinos Anastassiadis; Abdelkader Ayadi; James F. Battey; Cindy Bell; Marie-Christine Birling; Joanna Bottomley; Steve D. Brown; Antje Bürger; Carol J. Bult; Wendy Bushell; Francis S. Collins; et al. (Mammalian Genome, 2012)

A critical life stage of the Atlantic salmon Salmo salar : behaviour and survival during the smolt and initial post‐smolt migration - E. B. Thorstad; F. Whoriskey; I. Uglem; A. Moore; A. H. Rikardsen; B. Finstad (Journal of Fish Biology, 2012)
The anadromous life cycle of Atlantic salmon Salmo salar involves long migrations to novel environments and challenging physiological transformations when moving between salt‐free and salt‐rich waters. In this article, (1) environmental factors affecting the migration behaviour and survival of smolts and post‐smolts during the river, estuarine and early marine phases, (2) how behavioural patterns are linked to survival and (3) how anthropogenic factors affect migration and survival are synthesized and reviewed based on published literature. The timing of the smolt migration is important in determining marine survival. The timing varies among rivers, most likely as a consequence of local adaptations, to ensure sea entry during optimal periods. Smolts and post‐smolts swim actively and fast during migration, but in areas with strong currents, their own movements may be overridden by current‐induced transport. Progression rates during the early marine migration vary between 0·4 and 3·0 body lengths s −1 relative to the ground. Reported mortality is 0·3–7·0% (median 2·3) km −1 during downriver migration, 0·6–36% (median 6·0) km −1 in estuaries and 0·3–3·4% (median 1·4) km −1 in coastal areas. Estuaries and river mouths are the sites of the highest mortalities, with predation being a common cause. The mortality rates varied more among studies in estuaries than in rivers and marine areas, which probably reflects the huge variation among estuaries in their characteristics. Behaviour and survival during migration may also be affected by pollution, fish farming, sea lice Lepeophtheirus salmonis , hydropower development and other anthropogenic activities that may be directly lethal, delay migration or have indirect effects by inhibiting migration. Total mortality reported during early marine migration (up to 5–230 km from the river mouths) in the studies available to date varies between 8 and 71%. Hence, the early marine migration is a life stage with high mortalities, due to both natural and human influences. Factors affecting mortality during the smolt and post‐smolt stages contribute to determine the abundance of spawner returns. With many S. salar populations in decline, increased mortality at these stages may considerably contribute to limit S. salar production, and the consequences of human‐induced mortality at this stage may be severe. Development of management actions to increase survival and fitness at the smolt and post‐smolt stages is crucial to re‐establish or conserve wild populations.

Identification of the peptide-binding motif recognized by the pigtail macaque class I MHC molecule Mane-A1*082:01 (Mane A*0301) - Carrie Moore; John Sidney; A. Michelle English; Amanda Wriston; Donald F. Hunt; Jeffrey Shabanowitz; Scott Southwood; Kate Bradley; Bernard A. P. Lafont; Bianca R. Mothé; Alessandro Sette (Immunogenetics, 2012)

Photic resetting of the circadian clock is correlated with photic habitat in Anolis lizards - Ashli F. Moore; Michael Menaker (Journal of Comparative Physiology A, 2012)

Trace Metal Occurrence and Mobility Assessment in Stream Sediments near the Sungun Porphyry Copper Deposit in Northwest Iran - F. Moore; A. A. Aghazadeh (Mine Water and the Environment, 2012)

Photic induction of locomotor activity is correlated with photic habitat in Anolis lizards - Ashli F. Moore; Masashi Kawasaki; Michael Menaker (Journal of Comparative Physiology A, 2012)

Artificial gravity training reduces bed rest-induced cardiovascular deconditioning - Michael B. Stenger; Joyce M. Evans; Charles F. Knapp; Stuart M. C. Lee; Tiffany R. Phillips; Sondra A. Perez; Alan D. Moore; William H. Paloski; Steven H. Platts (European Journal of Applied Physiology, 2012)

Critical Thermal Maxima of aquatic macroinvertebrates: towards identifying bioindicators of thermal alteration - Helen F. Dallas; Nicholas A. Rivers-Moore (Hydrobiologia, 2012)

Effects of biotic disturbances on forest carbon cycling in the U nited S tates and C anada - Jeffrey A. Hicke; Craig D. Allen; Ankur R. Desai; Michael C. Dietze; Ronald J. Hall; Edward H. (Ted) Hogg; Daniel M. Kashian; David Moore; Kenneth F. Raffa; Rona N. Sturrock; James Vogelmann (Global Change Biology, 2012)
Forest insects and pathogens are major disturbance agents that have affected millions of hectares in N orth A merica in recent decades, implying significant impacts to the carbon ( C ) cycle. Here, we review and synthesize published studies of the effects of biotic disturbances on forest C cycling in the U nited S tates and C anada. Primary productivity in stands was reduced, sometimes considerably, immediately following insect or pathogen attack. After repeated growth reductions caused by some insects or pathogens or a single infestation by some bark beetle species, tree mortality occurred, altering productivity and decomposition. In the years following disturbance, primary productivity in some cases increased rapidly as a result of enhanced growth by surviving vegetation, and in other cases increased slowly because of lower forest regrowth. In the decades following tree mortality, decomposition increased as a result of the large amount of dead organic matter. Net ecosystem productivity decreased immediately following attack, with some studies reporting a switch to a C source to the atmosphere, and increased afterward as the forest regrew and dead organic matter decomposed. Large variability in C cycle responses arose from several factors, including type of insect or pathogen, time since disturbance, number of trees affected, and capacity of remaining vegetation to increase growth rates following outbreak. We identified significant knowledge gaps, including limited understanding of carbon cycle impacts among different biotic disturbance types (particularly pathogens), their impacts at landscape and regional scales, and limited capacity to predict disturbance events and their consequences for carbon cycling. We conclude that biotic disturbances can have major impacts on forest C stocks and fluxes and can be large enough to affect regional C cycling. However, additional research is needed to reduce the uncertainties associated with quantifying biotic disturbance effects on the N orth A merican C budget.

The Effects of Prenatal Alcohol Exposure on Behavior: Rodent and Primate Studies - Mary L. Schneider; Colleen F. Moore; Miriam M. Adkins (Neuropsychology Review, 2011)

Effects of Fluidized Gas Desulfurization (FGD) Gypsum on Non-Target Freshwater and Sediment Dwelling Organisms - S. L. Greenway; M. T. Moore; J. L. Farris; F. E. Rhoton (Bulletin of Environmental Contamination and Toxicology, 2011)

Speciation and Phytoavailability of Heavy Metals in Contaminated Soils in Sarcheshmeh Area, Kerman Province, Iran - F. Rastmanesh; F. Moore; B. Keshavarzi (Bulletin of Environmental Contamination and Toxicology, 2010)

Cloning and characterization of a sialidase from the filamentous fungus, Aspergillus fumigatus - Mark L. Warwas; Juliana H. F. Yeung; Deepani Indurugalla; Arne Ø. Mooers; Andrew J. Bennet; Margo M. Moore (Glycoconjugate Journal, 2010)

The effects of farming system, habitat type and bait type on the isolation of entomopathogenic fungi from citrus soils in the Eastern Cape Province, South Africa - T. A. Goble; J. F. Dames; M. P Hill; S. D. Moore (BioControl, 2010)

Assessment of heavy metal concentration in the Khoshk River water and sediment, Shiraz, Southwest Iran - S. Salati; F. Moore (Environmental Monitoring and Assessment, 2010)

Monitoring deterioration of vegetation cover in the vicinity of smelting industry, using statistical methods and TM and ETM+ imageries, Sarcheshmeh copper complex, Central Iran - F. Rastmanesh; F. Moore; M. Kharrati-Kopaei; M. Behrouz (Environmental Monitoring and Assessment, 2010)

Rhynchospora galeana, a new name for Rhynchospora breviseta (Gale) Channell (Cyperaceae) - Robert F. C. Naczi; Wesley M. Knapp; Gerry Moore (Brittonia, 2010)

Cliniconeuropathologic correlates of human immunodeficiency virus in the era of antiretroviral therapy - I Everall; F Vaida; N Khanlou; D Lazzaretto; C Achim; S Letendre; D Moore; R Ellis; M Cherner; B Gelman; S Morgello; E Singer; et al. (Journal of NeuroVirology, 2009)

Asenapine effects in animal models of psychosis and cognitive function - Hugh M. Marston; Jared W. Young; Frederic D. C. Martin; Kevin A. Serpa; Christopher L. Moore; Erik H. F. Wong; Lisa Gold; Leonard T. Meltzer; Marc R. Azar; Mark A. Geyer; Mohammed Shahid (Psychopharmacology, 2009)

Prospective study of physical activity and the risk of ovarian cancer - Michael F. Leitzmann; Corinna Koebnick; Steven C. Moore; Kim N. Danforth; Louise A. Brinton; Albert R. Hollenbeck; Arthur Schatzkin; James V. Lacey (Cancer Causes & Control, 2009)

Antioxidant vitamins and the risk of endometrial cancer: a dose–response meta-analysis - Elisa V. Bandera; Dina M. Gifkins; Dirk F. Moore; Marjorie L. McCullough; Lawrence H. Kushi (Cancer Causes & Control, 2009)

Autism Overflows with Syntheses - Matthew K. Belmonte; Yoram S. Bonneh; Yael Adini; Portia E. Iversen; Natacha A. Akshoomoff; Tal Kenet; Christopher I. Moore; Helen J. Simon; John F. Houde; Michael M. Merzenich (Neuropsychology Review, 2009)

Observations on the Estrogenic Activity and Concentration of 17β-Estradiol in the Discharges of 12 Wastewater Treatment Plants in Southern Australia - C. Mispagel; G. Allinson; M. Allinson; F. Shiraishi; M. Nishikawa; M. R. Moore (Archives of Environmental Contamination and Toxicology, 2009)

Mississippi Oxbow Lake Sediment Quality During an Artificial Flood - S. S. Knight; R. E. Lizotte; M. T. Moore; S. Smith; F. D. Shields (Bulletin of Environmental Contamination and Toxicology, 2009)

Intrascleral Drug Delivery to the Eye Using Hollow Microneedles - Jason Jiang; Jason S. Moore; Henry F. Edelhauser; Mark R. Prausnitz (Pharmaceutical Research, 2009)

Male–female differences in the genetic regulation of t-PA and PAI-1 levels in a Ghanaian population - J. A. Schoenhard; F. W. Asselbergs; K. A. Poku; S. A. Stocki; S. Gordon; D. E. Vaughan; N. J. Brown; J. H. Moore; Scott M. Williams (Human Genetics, 2008)

Biosynthesis of the respiratory formate dehydrogenases from Escherichia coli: characterization of the FdhE protein - Iris Lüke; Gareth Butland; Kevin Moore; Grant Buchanan; Verity Lyall; Shirley A. Fairhurst; Jack F. Greenblatt; Andrew Emili; Tracy Palmer; Frank Sargent (Archives of Microbiology, 2008)

Rainbow Smelt (Osmerus mordax) Genomic Library and EST Resources - K. R. von Schalburg; J. Leong; G. A. Cooper; A. Robb; M. R. Beetz-Sargent; R. Lieph; R. A. Holt; R. Moore; K. V. Ewart; W. R. Driedzic; B. F. H. ten Hallers; B. Zhu; et al. (Marine Biotechnology, 2008)
Genomic resources in rainbow smelt ( Osmerus mordax ) enable us to examine the genome duplication process in salmonids and test hypotheses relating to the fate of duplicated genes. They further enable us to pursue physiological and ecological studies in smelt. A bacterial artificial chromosome library containing 52,410 clones with an average insert size of 146 kb was constructed. This library represents an 11-fold average coverage of the rainbow smelt ( O. mordax ) genome. In addition, several complementary deoxyribonucleic acid libraries were constructed, and 36,758 sequences were obtained and combined into 12,159 transcripts. Over half of these transcripts have been identified, several of which have been associated with cold adaptation. These basic resources show high levels of similarity (86%) to salmonid genes and provide initial support for genome duplication in the salmonid ancestor. They also facilitate identification of genes important to fish and direct us toward new technologies for other studies in fish biology.

Reduced folate carrier 80A→G polymorphism, plasma folate, and risk of placental abruption - Cande V. Ananth; Morgan R. Peltier; Dirk F. Moore; Wendy L. Kinzler; Daniel Leclerc; Rima R. Rozen (Human Genetics, 2008)

Tectonics and sedimentation around Kashinosaki Knoll: A subducting basement high in the eastern Nankai Trough - Toshihiro Ike; Gregory F. Moore; Shin'ichi Kuramoto; Jin‐Oh Park; Yoshiyuki Kaneda; Asahiko Taira (Island Arc, 2008)
When seamounts and other topographic highs on an oceanic plate are subducted, they cause significant deformation of the overriding plate and may act as asperities deeper in the seismogenic zone. Kashinosaki Knoll (KK) is an isolated basement high of volcanic origin on the subducting Philippine Sea Plate that will soon be subducted at the eastern Nankai Trough. Seismic reflection imaging reveals a thick accumulation of sediments (∼1200 m) over and around the knoll. The lower portion of the sedimentary section has a package of high‐amplitude, continuous reflections, interpreted as turbidites, that lap onto steep basement slopes but are parallel to the gentler basement slopes. Total sediment thickness on the western and northern slopes is approximately 40–50% more than on the summit and southeastern slopes of KK. These characteristics imply that the basal sedimentary section northwest of KK was deposited by infrequent high‐energy turbidity currents, whereas the area southeast of KK was dominated by hemipelagic sedimentation over asymmetric basement relief. From the sediment structure and magnetic anomalies, we estimate that the knoll likely formed near the spreading center of the Shikoku Basin in the early Miocene. Its origin differs from that of nearby Zenisu Ridge, which is a piece of the Shikoku Basin crust uplifted along a thrust fault related to the collision of the Izu–Bonin arc and Honshu. KK has been carried into the margin of the Nankai Trough, and its high topography is deflecting Quaternary trench turbidites to the south. When KK collides with the accretionary prism in about 1 My, the associated variations in sediment type and thickness around the knoll will likely result in complex local variations in prism deformation.

Variations in sediment thickness and type along the northern Philippine Sea Plate at the Nankai Trough - Toshihiro Ike; Gregory F. Moore; Shin'ichi Kuramoto; Jin‐Oh Park; Yoshiyuki Kaneda; Asahiko Taira (Island Arc, 2008)
We documented regional and local variations in basement relief, sediment thickness, and sediment type in the Shikoku Basin, northern Philippine Sea Plate, which is subducting at the Nankai Trough. Seismic reflection data, tied with ocean drilling program drill cores, reveal that variations in the incoming sediment sequences are correlated with basement topography. We mapped the three‐dimensional seismic facies distribution and measured representative seismic sequences and units. Trench‐parallel seismic profiles show three regional provinces in the Shikoku Basin that are distinguished by the magnitude of basement relief and sediment thickness: Western ( 600 m sediment thickness), Central (>1500 m relief, ∼2000 m sediments), and Eastern (

Two canine CD1a proteins are differentially expressed in skin - Frank A. Looringh van Beeck; Dirk M. Zajonc; Peter F. Moore; Yvette M. Schlotter; Femke Broere; Victor P. M. G. Rutten; Ton Willemse; Ildiko Van Rhijn (Immunogenetics, 2008)

Mapping mineralogical alteration using principal‐component analysis and matched filter processing in the Takab area, north‐west Iran, from ASTER data - F. Moore; F. Rastmanesh; H. Asadi; S. Modabberi (International Journal of Remote Sensing, 2008)

Structure and expression of MHC class Ib genes of the central M region in rat and mouse: M4, M5, and M6 - Doris Lambracht-Washington; Yuki F. Moore; Kurt Wonigeit; Kirsten Fischer Lindahl (Immunogenetics, 2008)

Transgenic resistance to Citrus tristeza virus in grapefruit - Vicente J. Febres; Richard F. Lee; Gloria A. Moore (Plant Cell Reports, 2008)

Consumption of animal foods and endometrial cancer risk: a systematic literature review and meta-analysis - Elisa V. Bandera; Lawrence H. Kushi; Dirk F. Moore; Dina M. Gifkins; Marjorie L. McCullough (Cancer Causes & Control, 2007)

Diazinon Mitigation in Constructed Wetlands: Influence of Vegetation - M. T. Moore; C. M. Cooper; S. Smith; R. F. Cullum; S. S. Knight; M. A. Locke; E. R. Bennett (Water, Air, & Soil Pollution, 2007)

Dietary lipids and endometrial cancer: the current epidemiologic evidence - Elisa V. Bandera; Lawrence H. Kushi; Dirk F. Moore; Dina M. Gifkins; Marjorie L. McCullough (Cancer Causes & Control, 2007)

Spring‐neap modulation of internal tide mixing and vertical nitrate fluxes at a shelf edge in summer - Jonathan Sharples; Jacqueline F. Tweddle; J. A. Mattias Green; Matthew R. Palmer; Young-Nam Kim; Anna E. Hickman; Patrick M. Holligan; C. Mark Moore; Tom P. Rippeth; John H. Simpson; Vladimir Krivtsov (Limnology and Oceanography, 2007)
Measurements of the intra‐tidal and spring‐neap variation in the vertical flux of nitrate into the base of the sub‐surface chlorophyll maximum (SCM) were made at the shelf edge of the Celtic Sea, a region with strong internal mixing driven by an internal tide. The neap tide daily mean nitrate flux was 1.3 (0.9‐1.8, 95% confidence interval) mmol m ‐2 d ‐1 . The spring tide flux was initially estimated as 3.5 (2.3‐5.2, 95% confidence interval) mmol m ‐2 d ‐1 . The higher spring tide nitrate flux was the result of turbulent dissipation occurring within the base of the SCM as compared to deeper dissipation during neap tides and was dominated by short events associated with the passage of internal solitons. Taking into account the likely under‐sampling of these short mixing events raised the spring tide nitrate flux estimate to about 9 mmol m ‐2 d ‐1 . The neap tide nitrate flux was sufficient to support substantial new production and a considerable fraction of the observed rates of carbon fixation. Spring tide fluxes were potentially in excess of the capacity of the phytoplankton community to uptake nitrate. This potential excess nitrate flux during spring tides may be utilized to support new production during the lower mixing associated with the transition toward neap tide. The shelf edge is shown to be a region with a significantly different phytoplankton community as compared to the adjacent Celtic Sea and northeast Atlantic Ocean, highlighting the role of gradients in physical processes leading to gradients in ecosystem structure.

High efficiency Agrobacterium rhizogenes-mediated transformation of Saponaria vaccaria L. (Caryophyllaceae) using fluorescence selection - Janice F. Schmidt; Maria D. Moore; Lawrence E. Pelcher; Patrick S. Covello (Plant Cell Reports, 2007)

Chromosomal location and gene paucity of the male specific region on papaya Y chromosome - Qingyi Yu; Shaobin Hou; Roman Hobza; F. Alex Feltus; Xiue Wang; Weiwei Jin; Rachel L. Skelton; Andrea Blas; Cornelia Lemke; Jimmy H. Saw; Paul H. Moore; Maqsudul Alam; et al. (Molecular Genetics and Genomics, 2007)

A QTL on chromosome 6A in bread wheat (Triticum aestivum) is associated with longer coleoptiles, greater seedling vigour and final plant height - W. Spielmeyer; J. Hyles; P. Joaquim; F. Azanza; D. Bonnett; M. E. Ellis; C. Moore; R. A. Richards (Theoretical and Applied Genetics, 2007)

Effect of adenoviral mediated overexpression of fibromodulin on human dermal fibroblasts and scar formation in full-thickness incisional wounds - Alexander Stoff; Angel A. Rivera; J. Michael Mathis; Steven T. Moore; N. S. Banerjee; Maaike Everts; Antonio Espinosa-de-los-Monteros; Zdenek Novak; Luis O. Vasconez; Thomas R. Broker; Dirk F. Richter; Dale Feldman; et al. (Journal of Molecular Medicine, 2007)

The Stanley unconformity in Lake Huron basin: evidence for a climate-driven closed lowstand about 7900 14C BP, with similar implications for the Chippewa lowstand in Lake Michigan basin - C. F. M. Lewis; C. W. Heil; J. B. Hubeny; J. W. King; T. C. Moore; D. K. Rea (Journal of Paleolimnology, 2007)

Unobtrusive integration of data management with fMRI analysis - Andrew V. Poliakov; Xenia Hertzenberg; Eider B. Moore; David P. Corina; George A. Ojemann; James F. Brinkley (Neuroinformatics, 2007)

Genetic analysis of flowering and maturity time in high latitude spring wheat - Muhammad Iqbal; Alireza Navabi; Donald F. Salmon; Rong-Cai Yang; Brenda M. Murdoch; Steve S. Moore; Dean Spaner (Euphytica, 2007)

Validation of MERIS reflectance and chlorophyll during the BENCAL cruise October 2002: preliminary validation of new demonstration products for phytoplankton functional types and photosynthetic parameters - J. Aiken; J. R. Fishwick; S. Lavender; R. Barlow; G. F. Moore; H. Sessions; S. Bernard; J. Ras; N. J. Hardman‐Mountford (International Journal of Remote Sensing, 2007)

Topiramate raises anterior cingulate cortex glutamine levels in healthy men; a 4.0 T magnetic resonance spectroscopy study - Constance M. Moore; Megan Wardrop; Blaise deB. Frederick; Perry F. Renshaw (Psychopharmacology, 2007)

Invasion in a heterogeneous world: resistance, coexistence or hostile takeover? - Brett A. Melbourne; Howard V. Cornell; Kendi F. Davies; Christopher J. Dugaw; Sarah Elmendorf; Amy L. Freestone; Richard J Hall; Susan Harrison; Alan Hastings; Matt Holland; Marcel Holyoak; John Lambrinos; et al. (Ecology Letters, 2007)
We review and synthesize recent developments in the study of the invasion of communities in heterogeneous environments, considering both the invasibility of the community and impacts to the community. We consider both empirical and theoretical studies. For each of three major kinds of environmental heterogeneity (temporal, spatial and invader‐driven), we find evidence that heterogeneity is critical to the invasibility of the community, the rate of spread, and the impacts on the community following invasion. We propose an environmental heterogeneity hypothesis of invasions, whereby heterogeneity both increases invasion success and reduces the impact to native species in the community, because it promotes invasion and coexistence mechanisms that are not possible in homogeneous environments. This hypothesis could help to explain recent findings that diversity is often increased as a result of biological invasions. It could also explain the scale dependence of the diversity–invasibility relationship. Despite the undoubted importance of heterogeneity to the invasion of communities, it has been studied remarkably little and new research is needed that simultaneously considers invasion, environmental heterogeneity and community characteristics. As a young field, there is an unrivalled opportunity for theoreticians and experimenters to work together to build a tractable theory informed by data.

Fires in tropical forests – what is really the problem? lessons from Indonesia - L. Tacconi; P. F. Moore; D. Kaimowitz (Mitigation and Adaptation Strategies for Global Change, 2006)

The effects of chronic developmental hypoxia on swimming performance in zebrafish - S. Widmer; F. B.‐G. Moore; B. Bagatto (Journal of Fish Biology, 2006)
Relative to normoxia‐reared fish, hypoxia‐reared zebrafish Danio rerio achieved 24·9 and 21·4% slower maximal swim velocities in both normoxic and hypoxic waters, respectively. Hypoxia‐reared fish also produced 26·1 and 63·9% less lactate during resting conditions across both normoxic and hypoxic waters, respectively. During exercise, this trend continued as hypoxia‐reared fish produced 68·2 and 55·1% less lactate across both normoxic and hypoxic waters, respectively. This reduction in performance, rather than representing a purely pathological (maladaptive) response to hypoxia, appears to represent a fundamental shift in the metabolic response to hypoxia.

Flurbiprofen and its nitric oxide-releasing derivative protect against septic shock in rats - F. Anuar; M. Whiteman; M. Bhatia; P. K. Moore (Inflammation Research, 2006)

Topiramate raises anterior cingulate cortex glutamine levels in healthy men; a 4.0 T magnetic resonance spectroscopy study - Constance M. Moore; Megan Wardrop; Blaise deB. Frederick; Perry F. Renshaw (Psychopharmacology, 2006)

Neuropsychological function and delay discounting in methamphetamine-dependent individuals - William F. Hoffman; Meredith Moore; Raymond Templin; Bentson McFarland; Robert J. Hitzemann; Suzanne H. Mitchell (Psychopharmacology, 2006)

Morphology and response of roots of pasture species to phosphorus and nitrogen nutrition - J. O. Hill; R. J. Simpson; A. D. Moore; D. F. Chapman (Plant and Soil, 2006)

In vitro Survival and Growth of Salmonella Typhimurium inoculated on Yolk Membrane after long Term refrigerated Storage of Shell Eggs - Z. R. Howard; R. W. Moore; I. B. Zabala Diaz; W. K. Kim; S. G. Birkhold; J. A. Byrd; L. F. Kubena; D. J. Nisbet; S. C. Ricke (Journal of Consumer Protection and Food Safety, 2006)

Modeling postural instability with Galvanic vestibular stimulation - Hamish G. MacDougall; Steven T. Moore; Ian S. Curthoys; F. Owen Black (Experimental Brain Research, 2006)

A tumor vasculature targeted liposome delivery system for combretastatin A4: Design, characterization, and in vitro evaluation - Ramakrishna Nallamothu; George C. Wood; Christopher B. Pattillo; Robert C. Scott; Mohammad F. Kiani; Bob M. Moore; Laura A. Thoma (AAPS PharmSciTech, 2006)

A method for estimating inherent optical properties of New Zealand continental shelf waters from satellite ocean colour measurements - Matthew H. Pinkerton; Gerald F. Moore; Samantha J. Lavender; Mark P. Gall; Kadija Oubelkheir; Kenneth M. Richardson; Philip W. Boyd; James Aiken (New Zealand Journal of Marine and Freshwater Research, 2006)
We describe a method to estimate spectral absorption and backscattering coefficients between 412 and 555 nm from measurements of remote sensing reflectance across the visible spectrum. The algorithm described is applicable to ocean colour satellite measurements (e.g., SeaWiFS). In situ measurements of inherent and apparent optical properties were made at 19 coastal stations off the north coast of New Zealand's South Island in December 2001. These measurements were used to parameterise a bio‐optical model that estimates remote sensing reflectance from concentrations of water constituents. The model generated a large number (5000) of modelled ocean colour reflectance spectra that represented a greater range of biogeochemical conditions than were measured in the study area. These modelled values spanned a wide range of chlorophyll concentrations (0.1–10 mg m ‐3 ), total suspended particulate material concentrations (0.1–50 g m ‐3 ), and dissolved yellow substance absorptions (0.01–3 m ‐1 ). The modelled spectra were then used to test the performance of the algorithm. The median ratio of algorithm values to target values was 0.84 (absorption), and 0.80 (backscatter), and the median absolute errors were 33% (absorption) and 36% (backscatter) across two orders of magnitude. The r 2 values between target and algorithm values of inherent optical properties in log‐log space were 0.89 for backscatter, and varied with wavelength for absorption from 0.79 (412 nm), 0.72 (443 nm), 0.63 (490 nm), 0.55 (510 nm), and 0.21 (555 nm).

In vitro Survival and Growth of Salmonella Typhimurium inoculated on Yolk Membrane after long Term refrigerated Storage of Shell Eggs - Z. R. Howard; R. W. Moore; I. B. Zabala Diaz; W. K. Kim; S. G. Birkhold; J. A. Byrd; L. F. Kubena; D. J. Nisbet; S. C. Ricke (Journal of Consumer Protection and Food Safety, 2006)

The South African and Namibian Populations of the Resurrection Plant Myrothamnus flabellifolius are Genetically Distinct and Display Variation in Their Galloylquinic Acid Composition - John P. Moore; Jill M. Farrant; George G. Lindsey; Wolf F. Brandt (Journal of Chemical Ecology, 2005)

Low gene flow but high genetic diversity in the threatened Mallorcan midwife toad Alytes muletensis - F. J. L. KRAAIJEVELD‐SMIT; T. J. C. BEEBEE; R. A. GRIFFITHS; R. D. MOORE; L. SCHLEY (Molecular Ecology, 2005)
We investigated fine‐scale genetic structuring in the rare and vulnerable Mallorcan midwife toad Alytes muletensis using eight polymorphic microsatellite markers. The current range of this amphibian is restricted to some 19 sites of which six are derived from reintroductions, all located in the mountain ranges of Mallorca. We sampled tadpoles from 14 pools covering 10 natural sites and two reintroduction sites for microsatellite DNA analyses. Relatively high levels of genetic variation were found in most pools ( H E = 0.38–0.71, allelic richness = 2.6–6.2). Only at one pool has the population recently gone through a bottleneck. Dispersal between pools in different torrents does not occur whereas downstream dispersal between pools within the same torrent does happen at low frequencies. This occasional exchange of individuals does not lead to neighbouring pools in the same torrent being panmictic. This can be concluded because all F ST values (0.12–0.53) differ significantly from zero and structure analyses identified neighbouring pools as separate populations. Furthermore, assignment and migration tests showed little exchange between neighbouring pools. If upstream locations or complete torrents go extinct, they are unlikely to be recolonized naturally. For conservation purposes, reintroductions of tadpoles to sites where local extinctions have occurred may therefore be advisable.

Targeting of the Antivascular Drug Combretastatin to Irradiated Tumors Results in Tumor Growth Delay - Christopher B. Pattillo; Farid Sari-Sarraf; Ramakrishna Nallamothu; Bob M. Moore; George C. Wood; Mohammad F. Kiani (Pharmaceutical Research, 2005)

The spatial spread of invasions: new developments in theory and evidence - Alan Hastings; Kim Cuddington; Kendi F. Davies; Christopher J. Dugaw; Sarah Elmendorf; Amy Freestone; Susan Harrison; Matthew Holland; John Lambrinos; Urmila Malvadkar; Brett A. Melbourne; Kara Moore; et al. (Ecology Letters, 2005)
We review and synthesize recent developments in the study of the spread of invasive species, emphasizing both empirical and theoretical approaches. Recent theoretical work has shown that invasive species spread is a much more complex process than the classical models suggested, as long range dispersal events can have a large influence on the rate of range expansion through time. Empirical work goes even further, emphasizing the role of spatial heterogeneity, temporal variability, other species, and evolution. As in some of the classic work on spread, the study of range expansion of invasive species provides unique opportunities to use differences between theory and data to determine the important underlying processes that control spread rates.

Murine MHC classIb gene, H2-M2, encodes a conserved surface-expressed glycoprotein - Yuki F. Moore; Doris Lambracht-Washington; Piotr Tabaczewski; Kirsten Fischer Lindahl (Immunogenetics, 2004)

Distribution of hand location in monkeys during spontaneous behavior - Michael S. A. Graziano; Dylan F. Cooke; Charlotte S. R. Taylor; Tirin Moore (Experimental Brain Research, 2004)

Forest Certification of State and University Lands in North Carolina: A Comparison - F. Cubbage; S. Moore; J. Cox; L. Jervis; J. Edeburn; D. Richter; W. Boyette; M. Thompson; M. Chesnutt (Journal of Forestry, 2003)
North Carolina State University, Duke University, and the North Carolina Division of Forest Resources (DFR) recently received both Forest Stewardship Council (FSC) and Sustainable Forestry Initiative (SFI) certification for their forests. Meeting SFI standards required better environmental management systems, improved use of best management practices, and better recordkeeping but few subsequent forest management changes. FSC required about the same environmental system changes but more forest management changes to favor future natural stand management and biodiversity protection. Costs included changes in forest management and recordkeeping to achieve forest certification, inspection expenses, prescribed changes in forest management, forgone timber revenues, and more stakeholder consultation. Benefits can include an improved professional reputation, better worker safety and training, better records and processes, more active public involvement, enhanced knowledge for outreach, better environmental management systems, more holistic management, and perhaps higher timber prices or greater market access.

Environmental variability and biogeography: the relationship between bathymetric distribution and geographical range size in marine algae and gastropods - Christopher D. G. Harley; Katherine F. Smith; Vicki L. Moore (Global Ecology and Biogeography, 2003)
Aims Gradients of environmental variability have been proposed to explain spatial variation in patterns of geographical range size. We explore this relationship in NE Pacific algae and NW Atlantic gastropods by using the characteristics of species’ bathymetric distributions as a proxy for tolerance of environmental variability. Location NE Pacific and NW Atlantic. Methods Data on species bathymetric and geographical distributions were compiled from the literature. Results For both algae and gastropods, species that inhabit highly seasonal, shallow depth zones have broader latitudinal ranges, and occupy more biogeographical provinces, than species that live in more temporally stable, deeper zones. Furthermore, species that tolerate spatial variability along the bathymetric axis, i.e. those that occur in multiple depth zones, have broader geographical ranges than species restricted to fewer depth zones. Main conclusions Within‐range environmental variability, through both space and time, is predictive of large geographical ranges for marine algae and gastropods. Analysis of species distributions across perpendicular gradients (e.g. depth and latitude) is a powerful approach to discerning the mechanisms that govern biogeographical patterns, and provides easily obtainable broad‐brush predictions regarding the biogeographical outcomes of global change.

Genetic relationships of macadamia cultivars and species revealed by AFLP markers - D.L. Steiger; P.H. Moore; F. Zee; Z. Liu; R. Ming (Euphytica, 2003)

Sedimentary Nonylphenol Contamination in an Urbanized, Industrialized Segment of the Delaware River Estuary, USA - J. T. F. Ashley; A. Moore; H. M. Stapleton; D. J. Velinsky; M. P. Wilhelm (Bulletin of Environmental Contamination and Toxicology, 2003)

Projecting future fire activity in Amazonia - MANOEL F. CARDOSO; GEORGE C. HURTT; BERRIEN MOORE; CARLOS A. NOBRE; ELAINE M. PRINS (Global Change Biology, 2003)
Fires are major disturbances for ecosystems in Amazonia. They affect vegetation succession, alter nutrients and carbon cycling, and modify the composition of the atmosphere. Fires in this region are strongly related to land‐use, land‐cover and climate conditions. Because these factors are all expected to change in the future, it is reasonable to expect that fire activity will also change. Models are needed to quantitatively estimate the magnitude of these potential changes. Here we present a new fire model developed by relating satellite information on fires to corresponding statistics on climate, land‐use and land‐cover. The model is first shown to reproduce the main contemporary large‐scale features of fire patterns in Amazonia. To estimate potential changes in fire activity in the future, we then applied the model to two alternative scenarios of development of the region. We find that in both scenarios, substantial changes in the frequency and spatial patterns of fires are expected unless steps are taken to mitigate fire activity.

Insect Conservation in an Urban Biodiversity Hotspot: The San Francisco Bay Area - Edward F. Connor; John Hafernik; Jacqueline Levy; Vicki Lee Moore; Jancy K. Rickman (Journal of Insect Conservation, 2002)

Utilization of different nitrogen sources by the marine cyanobacteria Prochlorococcus and Synechococcus - Lisa R. Moore; Anton F. Post; Gabrielle Rocap; Sallie W. Chisholm (Limnology and Oceanography, 2002)
Prochlorococcus is the most abundant phytoplankter throughout the photic zone in stratified marine waters and experiences distinct gradients of light and nitrogen nutrition. Physiologically and genetically distinct Prochlorococcus ecotypes partition the water column: high‐B/A (low‐light adapted) ecotypes are generally restricted to the deep euphotic zone near or at the nitracline. Low‐B/A (high‐light adapted) ecotypes predominate in, but are not limited to, NO 3 - ‐depleted surface waters, where they outnumber coexisting Synechococcus populations. The niche partitioning by different Prochlorococcus ecotypes begs the question of whether they also differ in their nitrogen (N) utilization physiology, especially with respect to NO 3 - utilization. To explore this possibility, we studied the capabilities of different Prochlorococcus and Synechococcus strains to grow on a variety of N sources. We found that all the isolates grew well on NH 4 + and all were capable of urea utilization, occasionally at a lower growth rate. None of the Prochlorococcus isolates were able to grow with NO 3 - . Four high‐B/A Prochlorococcus isolates grew on NO 3 - , but all others did not. Whole genome analysis of the low‐B/A Prochlorococcus MED4 revealed that the genes required for NO uptake and reduction were absent. The genome of the high‐B/A Prochlorococcus MIT 9313 also lacked the NO 3 - utilization genes but has homologs of genes required for NO 3 - utilization consistent with its physiology and ecology. Thus, the utilization of different N sources in the marine environment is partitioned among closely related ecotypes, each with adaptations optimized for the environment where these sources are available.

Demonstration of Heterogeneous Genotypes of Taylorella equigenitalis Isolated from Horses in Six European Countries by Pulsed-Field Gel Electrophoresis - S. Kagawa; F. Klein; L. Corboz; J.E. Moore; O. Murayama; M. Matsuda (Veterinary Research Communications, 2001)

Construction and characterization of a papaya BAC library as a foundation for molecular dissection of a tree-fruit genome - R. Ming; P. H. Moore; F. Zee; C. A. Abbey; H. Ma; A. H. Paterson (Theoretical and Applied Genetics, 2001)

Polychlorinated dibenzodioxins and dibenzofurans in butter from different states in Australia - Jochen F. Müller; Joelle Prange; Caroline Gaus; Michael R. Moore; Olaf Päpke (Environmental Science and Pollution Research, 2001)

Spatial variations of the décollement/protodécollement zone and their implications: A 3‐D seismic inversion study of the northern Barbados accretionary prism - Zhiyong Zhao; Gregory F. Moore; Nathan L. B. Bangs; Thomas H. Shipley (Island Arc, 2000)
We conducted a 3‐D seismic inversion study to investigate spatial variations of physical properties of the décollement zone (DZ) and protodécollement zone (PDZ) under the northern Barbados accretionary prism. Significant spatial variations of physical properties were observed in the PDZ seaward of the thrust front from the inversion data. The density generally increases southward with a few localized low‐density patches. A lower density commonly corresponds to a thicker PDZ, suggesting that the paleomorphology may at least partially control the variations of the physical properties. Similar low‐density patches were also found in the DZ. These features may be inherited from those of the PDZ and enhanced after subduction through localized arrested consolidation. Under the prism toe, the density of the DZ increases landward. This trend may mainly result from shear‐induced consolidation of the DZ but may also be related to landward increasing tectonic loading. Significant north–south differences in density and, thus, porosity and strength of the PDZ, are observed and these differences may continue into the DZ. A stronger DZ is likely responsible for a larger prism taper observed in the southern area of the prism toe. The larger taper, thus more horizontal shortening, coupled with a thinner sediment sheet above the PDZ in the southern area, may cause a relative retreat of the thrust front and a pronounced change in strike of the sequence thrusts south of seismic Line 690. The north–south differences may ultimately have originated in the approach of a structurally higher segment of the Tiburon Rise. The Tiburon Rise affects regional morphology and, thus, it controls the sedimentation and physical properties of the PDZ. It may also control sediment accumulation above the PDZ. Therefore, the sedimentational change induced by the structural high of the Tiburon Rise, in turn, resulted in structural change of the prism in the southern area.

Screening for intron‐length polymorphisms in penaeid shrimps using exon‐primed intron‐crossing (EPIC)‐PCR - N. Bierne; S. A. Lehnert; E. Bédier; F. Bonhomme; S. S. Moore (Molecular Ecology, 2000)

The Kuh-e-Surmeh mineralization, a carbonate-hosted Zn-Pb deposit in the Simply Folded Belt of the Zagros Mountains, SW Iran - S. Liaghat; F. Moore; M. Jami (Mineralium Deposita, 2000)

The Parasite Moniliformis moniliformis Alters the Escape Response of its Cockroach Host Periplaneta americana - F. Libersat; J. Moore (Journal of Insect Behavior, 2000)

Characterization and radiation resistance of new isolates of Rubrobacter radiotolerans and Rubrobacter xylanophilus - A. C. Ferreira; M. F. Nobre; E. Moore; F. A. Rainey; J. R. Battista; M.S. da Costa (Extremophiles, 1999)

The influence of chronic anaemia on catecholamine secretion in the rainbow trout ( Oncorhynchus mykiss ) - S. F. Perry; C. J. Montpetit; A. E. Julio; K. Moore (Journal of Comparative Physiology B, 1999)

Hybrid GPS + GLONASS - Alan H. Dodson; Terry Moore; David F. Baker; John W. Swann (GPS Solutions, 1999)

Pharmacological evaluation of 1-(carboxymethyl)-3,5-diphenyl-2-methylbenzene, a novel arylacetic acid with potential anti-inflammatory properties - S. J. Cutler; C. DeWitt Blanton Jr.; D. T. Akin; F. B. Steinberg; A. B. Moore; J. A. Lott; T. C. Price; S. W. May; S. H. Pollock (Inflammation Research, 1998)

Acute and Chronic Toxicity of Azinphos-Methyl to Two Estuarine Species, Mysidopsis bahia and Cyprinodon variegatus - M. G. Morton; F. L. Mayer, Jr.; K. L. Dickson; W. T. Waller; J. C. Moore (Archives of Environmental Contamination and Toxicology, 1997)

A preliminary investigation of siliceous microfossil succession in late Quaternary sediments from Lake Baikal, Siberia - M. L. Julius; E. F. Stoermer; S. M. Colman; T. C. Moore (Journal of Paleolimnology, 1997)

Tenidap inhibits 5-lipoxygenase product formation in vitro, but this activity is not observed in three animal models - T. J. Carty; F. J. Sweeney; R. J. Griffiths; J. D. Eskra; M. J. Ernest; J. S. Pillar; J. D. Cheng; L. D. Loose; P. A. Joseph; P. P. Pazoles; P. F. Moore; A. Nagahisa; et al. (Inflammation Research, 1997)

A medium-density genetic linkage map of the bovine genome - W. Barendse; D. Vaiman; S. J. Kemp; Y. Sugimoto; S. M. Armitage; J. L. Williams; H. S. Sun; A. Eggen; M. Agaba; S. A. Aleyasin; M. Band; M. D. Bishop; et al. (Mammalian Genome, 1997)

Mating strategies and mating success of fallow (Dama dama) bucks in a non-lekking population - N. P. Moore; P. F. Kelly; J. P. Cahill; T. J. Hayden (Behavioral Ecology and Sociobiology, 1995)

Mating strategies and mating success of fallow ( Dama dama ) bucks in a non-lekking population - N. P. Moore; P. F. Kelly; J. P. Cahill; T. J. Hayden (Behavioral Ecology and Sociobiology, 1995)

Coastal Chip: A chipping potato variety resistant to heat stress - K. G. Haynes; R. W. Goth; S. B. Sterrett; B. J. Christ; D. E. Halseth; G. A. Porter; M. R. Henninger; D. R. Wilson; R. E. Webb; D. F. Hammond; R. Moore; F. L. Haynes; et al. (American Journal of Potato Research, 1992)

Proteins expressed by Mill Door/79 virus, a Kemerovo serogroup orbivirus transmitted by the ticksIxodes uriae - R. P. Spence; J. S. K. Pullin; N. F. Moore (Archives of Virology, 1986)

The proteins expressedin vivo andin vitro by an orbivirus of the Kemerovo serogroup isolated fromIxodes uriae ticks from St. Abb's Head, Scotland - S. M. Eley; P. A. Nuttall; N. F. Moore (Archives of Virology, 1985)

The biochemistry of orbiviruses - R. P. Spence; N. F. Moore; Patricia A. Nuttall (Archives of Virology, 1984)

Cell-free translation ofDrosophila C virus RNA: Identification of a virus protease activity involved in capsid protein synthesis and further studies onin vitro processing of Cricket paralysis virus specified proteins - B. Reavy; N. F. Moore (Archives of Virology, 1983)

The small RNA-viruses of insects - N. F. Moore; T. W. Tinsley (Archives of Virology, 1982)

The proteins expressed by different isolates ofDrosophila C virus - N. F. Moore; J. S. K. Pullin; W. A. L. Crump; N. Plus (Archives of Virology, 1982)

In vitro translation of cricket paralysis virus RNA - B. Reavy; N. F. Moore (Archives of Virology, 1981)

In vivo andin vitro synthesis of the proteins expressed by the RNA of black beetle virus - W. A. L. Crump; N. F. Moore (Archives of Virology, 1981)

The intracellular proteins induced by cricket paralysis virus inDrosophila cells: The effect of protease inhibitors and amino acid analogues - N. F. Moore; J. S. K. Pullin; B. Reavy (Archives of Virology, 1981)

Processing of Cricket paralysis virus induced polypeptides inDrosophila cells: Production of high molecular weight polypeptides by treatment with iodoacetamide - N. F. Moore; B. Reavy; J. S. K. Pullin (Archives of Virology, 1981)

Prediction of potato yield using temperature and insolation data - T. K. Hartz; F. D. Moore (American Journal of Potato Research, 1978)

Human carbonic anhydrases. VII. A new C type isozyme in erythrocytes of American Negroes - Mary Jane Moore; S. Funakoshi; H. F. Deutsch (Biochemical Genetics, 1971)

How can we interpret the zero tolerance for bacterial ring rot in certified seed potatoes - C. E. Logsdon; H. W. Poulsen; John J. Adams; J. W. Scannell; C. W. Frutchey; Robert Hickman; T. C. Blackburn; J, L. Robinson; E. L. Newdick; Paul J. Eastman; L. O. Weaver; H. C. Moore; et al. (American Journal of Potato Research, 1957)

The menominee potato: A new variety resistant to common scab and late blight - E. J. Wheeler; F. J. Stevenson; H. C. Moore (American Journal of Potato Research, 1944)

Crop and market news - B. A. Brown; H. C. Moore; P. N. Davis; J. F. Sharples; H. O. Werner; O. C. Hicks; J. Gilbert Borton; H. C. Odell; E. V. Hardenburg (American Journal of Potato Research, 1926)

Disease control and seed improvement number - F. A. Krantz; Donald Folsom; Daniel Dean; H. C. Moore; J. Tucker; J. W. Weston; H. R. Talmage; George L. Zundel; M. F. Barrus; G. L. Tiebout; Walter M. Peacock; C. L. Fitch; et al. (American Journal of Potato Research, 1925)

Brighter outlook for potatoes - J. G. Lipman; H. O. Werner; E. P. Miller; Walter M. Peacock; Julian Dimock; R. F. Howard; R. G. Newton; Wm. H. Martin; George H. Valentine; Dee Crane; O. C. Hicks; H. C. Moore (American Journal of Potato Research, 1925)

Potato notes - C. Tice; H. G. Zuckerman; W. C. Edmundson; W. L. Floyd; G. W. Waller; A. J. Johnston; E. P. Miller; E. A. Stokdyk; G. L. Tiebout; H. C. Moore; Walter M. Peacock; Andrew Schnetzler; et al. (American Journal of Potato Research, 1925)

Potato notes - Lou D. Sweet; J. H. Woolf; A. E. Wilkinson; F. C. Gaylord; E. A. Stodyke; R. D. Hews; H. C. Moore; J. W. Weston; W. V. Longley; J. Norton Woodruff; W. H. Martin; J. C. Crissey; et al. (American Journal of Potato Research, 1924)

Potato notes - J. T. Rosa; C. Tice; A. E. Wilkinson; B. G. Southwick; E. A. Stokdyk; Ray D. Hews; E. L. Newdick; W. Stuart; H. C. Moore; H. O. Werner; J. F. Hockey; C. L. Bailey; et al. (American Journal of Potato Research, 1924)